Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

Indole alkaloids from the roots of Nauclea officinalis and their chemotaxonomic significance - Shan-Ze Yin; Bao-Chan Liu; Guo-Lan Ma; Jiu-Wei Ma; Xi-Yang Lei; Bin-Bao Wang; Rui Li; Shao-Jie Lu; Wei-Min Gao; Pei-Gang Ouyang; Cai-Feng Ding (Biochemical Systematics and Ecology, 2026)

Astragaloside IV pretreatment enhances the therapeutic efficacy of bone marrow mesenchymal stem cells in murine fulminant hepatic failure - Ting-Ting Zhao; Wen-Qiang He; Rui-Zhi Shi; Bing-Yu Du; Mei-Mei Lan; Dan Zhou; Xiao-Qin Gao; Min Li; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Hypoxia-preconditioned bone marrow mesenchymal stem cells alleviate acute liver failure in association with the VEGF/c-Met pathway - Mei-Mei Lan; Rui-Zhi Shi; Zhe-Yu Li; Wen-Jun Qiao; Yong-Juan Guan; Wen-Qiang He; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Balancing fermentation control and aroma complexity in semi-spontaneous kiwifruit fermentation through Saccharomyces cerevisiae inoculum level - Wanju Yan; Yuanjing Li; Zitong Zhang; Rou Cai; Sinuo Feng; Jia Han; Wangsheng Sun; Rui Cai; Zhouli Wang; Jing Guo (Food Research International, 2026)

Built-in electric field for synergistically regulating electronic structure and interfacial hydrogen-bond network toward ampere-level current anion exchange membrane water electrolysis - Yujie Liang; Xinyu Lao; Jiaying Zhang; Hao Feng; Rui Min; Jingjing Wang; Yingying Zheng; Jiaqi Pan; Chaorong Li; Jun Cao (Chemical Engineering Journal, 2026)

Exploring metro station ridership: the role of network attraction and factor interactions - Lu Zhao; Wenfei Zhao; Rui Li; Zijia Wang; Linmu Zou; Feng Chen; Yizhe Wang (Transportation Research Part D: Transport and Environment, 2026)

Structurally diverse sesquiterpenoids from Curcuma longa and their anti-inflammatory activities - Guang-Han Li; Chun-Mei Qiu; Guang-Xu Wu; Miao Dai; Rui Feng; Hai-Guo Su; Liang Xiong (Phytochemistry, 2026)

One-step hydrophilic network for simultaneous boost in scaling prone cation removal and resistance to organic fouling of nanofiltration membranes - Rui Yu; Haonan Zhang; Yanqi Gan; Xupan Wang; Tian Wang; Jiahe Li; Mengqi Shi; Chenxi Dong; Feng Wu (Journal of Environmental Chemical Engineering, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Engineering pH-responsive probiotic carriers for oral delivery: Design principles, gastrointestinal fate, and translational perspectives - Ying Feng; Rui Chen; Liming Zhang; Dongze Li; Jinlong Xu; Yongkai Yuan (Food Research International, 2026)

Multi-omics combined with simulated fermentation model for elucidation of variation patterns of lipids and volatiles and its mechanism during black tea fermentation - Linchi Niu; Yuning Feng; Shan Zhang; Zhizhen Fang; Rui Liang; Zhenxing Xu; Xujiang Shan; Qinghua Zhou; Haibo Yuan; Yongwen Jiang; Jia Li (Food Chemistry, 2026)

Residues, drivers, and health implications of herbicides in typical black soil regions of China: Soil-crop system linkage and targeted human risk - Le Jian; Hanqiang Liu; Wenyou Hu; Peter E. Holm; Rui Li; Wenxue Niu; Feng Liu; Yuguo Zhao; Yongcun Zhao; Biao Huang (Environmental Pollution, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Future climate change reshapes agroclimatic resources and intensifies waterlogging impacts on crop production - Chunhu Wang; Rui Yang; Matthew Tom Harrison; De Li Liu; Puyu Feng; Meixue Zhou; Yunbo Zhang; Jiangwen Nie; Ke Liu (European Journal of Agronomy, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Personalized or pragmatic? A critical review of machine learning and metric-based models for indoor thermal comfort estimation - Rui Li; Haibo Feng (Building and Environment, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

A robust method for the simultaneous quantification of 30 legacy and emerging per- and polyfluoroalkyl substances (PFAS) across multiple marine media - Nuo Chen; Jing-Chun Feng; Li Tang; Rui Hou; Si Zhang (Marine Pollution Bulletin, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Multi-omics integration of flavor metabolome and lipidome elucidates 1-methylcyclopropene effects on postharvest quality in yellow-fleshed peach at 30 °C - Xianan Zhang; Rui Han; Zhengwen Ye; Mingshen Su; Huijuan Zhou; Jihong Du; Minghao Zhang; Feng Leng; Huayu Liu; Xiongwei Li (Food Research International, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

From vision to physics: Generative occupant modeling and 3D spatial data architecture in indoor environments - Rui Li; Lu Tang; Haibo Feng (Energy and Buildings, 2026)

Bioinspired antibacterial hydrogel empowered by switchable cerium-based nanoreactors for infected diabetic wound healing - Pengqin Xu; Longbao Feng; Yakupu Aobuliaximu; Minjian Liao; Yuejia Wu; Qiong Li; Chunmao Han; Rui Guo; Xingang Wang (Chemical Engineering Journal, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Toddacoumalins A-J, ten undescribed coumarins from the roots of Toddalia asiatica - Feng Wu; Han Yao; Xin-Rui Liao; Nan An; Xing-Shu Li; Wen-Hao Hu; Albert S.C. Chan; Hou-Jin Li; Wen-Jian Lan (Phytochemistry, 2026)

Preparation of P507-containing monodisperse magneto-permeable polystyrene swelling microspheres for extraction of low-concentration scandium from simulated red mud liquor - Jie Wang; Jinghan Ren; Rui Feng; Chenxi Li; Chenxin Shi; Mingqi Guo; Tianlei Yang; Yueping Guan (Journal of Water Process Engineering, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Targeted domestication of Enterobacter-dominated consortia for enhanced uranium immobilization via phosphate-mediated biomineralization - Jinxin Li; Jianhong Ma; Guicheng He; Qinglin Zhang; Han Qin; De Li; Rui Wang; Wei Zhang; Hui Zhang; Yongdong Wang; Feng Li; Yongmei Li (Journal of Hazardous Materials, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Mechanistic study on direct oxidation of xylose to xylonic and xylaric acids in base-free medium - Yinghao Wang; Wei Yu; Zhaozhe Li; Rui Min; Wenmao Zhang; Chunmei Li; Feng Du; Wenjuan Yan; Xin Jin; Chaohe Yang (Chemical Engineering Journal, 2026)

Aerobic extracellular electron transfer in Shewanella spp. - Wei Chen; Biyi Zhao; Liping Dai; Junpeng Li; Rui Bai; Fan Yang; Xudong Zhou; Jens Ulstrup; Feng Zhao; Yong Xiao (Bioresource Technology, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

Autophagy dysfunction in pancreatic acinar cells in acute pancreatitis: from molecular mechinery and trypsinogen activation to heterogeneity and therapeutic implications - Yuping Feng; Wen Guo; Rui Wu; Tingting Tan; Chen Tang; Li Zhang (Journal of Molecular Histology, 2026)

Dendrobium officinale leaf extract extends the mean lifespan in Caenorhabditis elegans via the DAF-16/SOD-3 axis - Cheng Gong; Shu Feng; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Shikuan Zhao; Rui Zhou; Li Feng; Yunfei Ge; Ruijuan Yang; Chongye Fang; Xiaocui Du (Biogerontology, 2026)

Exogenous sodium nitroprusside alleviates cadmium toxicity in Solanum nigrum via antioxidant activation, metal redistribution, and gene expression modulation - Fang Yang; Jie Zou; Jinqun Feng; Ting Yu; Shuai Zhang; Shunqin Zhu; Wanhong Liu; Rui Li (Protoplasma, 2026)

A review of visual navigation for agricultural robots in open fields and controlled environments - Rui-Feng Wang; Rui Xu; Peng W. Chee; Haihua Wang; Changying Li (Computers and Electronics in Agriculture, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

3D analytical modeling of seismic ground motion and energy partitioning in the marine site subjected to obliquely P-SV waves - Guang-rui Feng; Li-quan Xie; Chen-wei Luo (Soil Dynamics and Earthquake Engineering, 2026)

LDLR family proteins: the REAL receptors for orthoflavivirus entry - Xiang Chen; Rui-Ting Li; Cheng-Feng Qin (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Extent of soil disturbance and spatial strength degradation induced by spudcan penetration and extraction in clay - Cheng-feng Li; Rui Zhou; Run Liu; Hai-yang Zhang; Peng-cheng Ma (Ocean Engineering, 2026)

A pre-LECA origin of giant viruses as revealed by polymerase-based time tree - Xiaojun Wang; Xiaoyuan Feng; Zhichao Zhou; Meng Li; Rui Zhang (Molecular Phylogenetics and Evolution, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Uncovering the climate vulnerability of China’s poverty alleviation frontiers - Feng Zhao; Lijun Zuo; Yuyu Zhou; Liangzhi You; Huabing Huang; Rui Sun; Yuanyuan Zhao; Xunhuan Li; Dawei Zhang; Ran Meng (Global Environmental Change, 2026)

Amelioration of obesity-induced endothelial dysfunction by a synthetic ocean-derived peptide via regulating PPARα/γ pathway - Tiantian Zhou; Xinyi Chen; Yuehan Wang; Xutao Zhang; Lingchao Miao; Rui Tian; Yumeng Li; Yingying Feng; Xin Wu; Wai San Cheang (Food Research International, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

Enhanced deep nitrogen removal from low C/N wastewater via manganese-catalyzed iron-carbon micro-electrolysis coupled biological system: performance, mechanism, and microbial adaptability - Hengyuan Liu; Kai Wang; Feng Sha; Haibing Che; Rui Sun; Xiuhua Li (World Journal of Microbiology and Biotechnology, 2026)

Self-powered electron transfer on single-atom dual-reaction center: Achieving high-efficiency catalysis in oxidant-free systems - Wen Song; Enyu Zhao; Qinyi Wang; Pijun Duan; Xuguang Li; Tao Yan; Yanxia Zhao; Rui Feng; Yunhui Zhang; Yuanyuan Qu; Xing Xu; Liangguo Yan (Water Research, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Upcycling alumina industrial solid waste into vanadium disulfide anode materials for lithium-ion batteries - Runxin Zhang; Xuesong Li; Yuhan Wu; Feng Liu; Weishan Li; Pengfei Wang; Laishi Li; Fa-Nian Shi; Rui Xu; Yusheng Wu (Resources, Conservation and Recycling, 2026)

Nitrated apricot shell carbon catalyzes ketalization: Unraveling the reaction mechanism and pathways - Dongliang Duan; Guangxue Yang; Zhengping Dong; Rui Feng; Chuang Zhu; Yuxuan Li; BoYang Sun; Hongwei Zhao; Huanye Zhong (Journal of Environmental Chemical Engineering, 2026)

Innovations in arid land salinization management: Xinjiang's evolving paradigm for saline-alkali land governance - Jiandong Yu; Jihong Zhang; Zhenhua Wang; Li Guo; Jinzhu Zhang; Zhengjiang Feng; Yue Wen; Rui Chen; Xiaoguo Mu (Journal of Cleaner Production, 2026)

Highly efficient and selective adsorption of potassium ions from phosphoric acid by Amberlyst 36 resin - Lulu Feng; Xiaoyuan Zhang; Jingxia Huo; Shan Gao; Yawen Wang; Houfen Li; Rui Li; Jianxin Liu; Jiancheng Wang (Journal of Environmental Chemical Engineering, 2026)

Manganese oxide reduction by non-extracellular respiratory bacteria and fraxetin from plant residues decomposition - Wei Chen; Rui Bai; Xudong Zhou; Biyi Zhao; Chongyuan Ren; Junpeng Li; Liping Dai; Yacen Fang; Jing Zhang; Andreas Kappler; Feng Zhao; Yong Xiao (Journal of Environmental Sciences, 2026)

Anti-adhesion nanofiltration membranes via a fluorine-rich microenvironment for broad-Spectrum micropollutant removal - Yanqi Gan; Rui Yu; Xupan Wang; Tian Wang; Jiahe Li; Feng Wu; Mengqi Shi (Chemical Engineering Journal, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

Research on Dynamic Control of Flood Control Level for Jinxia Reservoir Group Considering Risks - Min Li; Yue Sun; Rui Feng; Wei Ding; Qianning Wang; Jinnan Zhang; Yong Peng; Feilin Zhu (Water Resources Management, 2026)

Rhizosphere microbial carbon utilization stimulates soil phosphorus fraction transformation in response to maize (Zea mays L.) and soybean (Glycine max.) interspecific interactions - Ruixue Wang; Lizhen Su; Dingjin Li; Zikun Yang; Rui Feng; Yi Zheng; Li Tang (Plant and Soil, 2026)

Dual Low-b-value-driven U-shaped fusion GAN for synthesizing high-b-value prostate DWI - Rui Feng; Qun Huang; Aiping Chen; Chuanbing Wang; Leilei Zhou; Jingjing Xu; Xiaodong Wang; Da Cao; Xiuhan Li; Wei Wang (Physical and Engineering Sciences in Medicine, 2026)

Failure mechanism and damage assessment of talus slopes with varied gradation under seismic loading - Xing Wei; Shitao Cheng; Rui Chen; Xinle Zhai; Jun Feng; Zijian Wang; Yanjun Li; Le Cheng (Landslides, 2026)

Effect of two double-stranded RNA viruses on the virulence of the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Yunxia Ni; Xintao Liu; Hui Zhao; Xingbei Zhao; Rui Qiu; Siyuan Feng; Xiaoyuan Tian; Shouye Song; Shujun Li; Hongyan Liu (Archives of Virology, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Enhancing freeze–thaw durability of concrete in plateau environments using superabsorbent polymer and nano-silica: pore structure optimization from micro- to macro-scale - Liangliang Li; Zetong Feng; Bin Wang; Rui He (Transportation Geotechnics, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

A safety evaluation study of Torulopsis globosa during the fermentation process of soy sauce - Rui Lian; Zhanyu Shen; Nana Bie; Jingyao Li; Xiaojuan Feng; Chunling Wang (Food Bioscience, 2026)

Smart pectinase-responsive chitosan nanocomposites packaging film for targeted preservation of refrigerated tilapia - Tingting Yang; Ye Cao; Yitian Chen; Xinming Zhang; Jiamei Wang; Aiguo Feng; Liming Zhang; Shuhuai Li; Xionghui Ma; Rui Chen (Chemical Engineering Journal, 2026)

Bio-inspired Zeta potential-matched design of natural rubber thermal interface materials with a compressed electrical double-layer for ultra-high thermal management capabilities - Rizheng He; Dongsheng Tian; Rui Tan; Bingxu Liu; Xinluo Yu; Huixing Li; Yaqing Liu; Dong An; Wei Feng; Chingping Wong (Chemical Engineering Journal, 2026)

Synergistic effect of tetrapropylammonium hydroxide and urea on hemicellulose fractionation with high-purity and high molecular weight - Rui Tian; Yi Ding; Bolang Zhu; Zhenhua Su; Baozhong Lü; Jing Bian; Mingfei Li; Zhengjun Shi; Pai Peng; Yuetong Kang; Feng Peng (Carbohydrate Polymers, 2026)

Molecular Basis of Biostimulant-enhanced Recovery from Late-spring Frost in Vitis Vinifera: A Transcriptomic Dissection - Chaoyue Feng; Xi Chen; Xinyi Luo; Huiyu Zhu; Huiling Ma; Xiaojun Liu; Yulong Li; Quan Sun; Rui Wang; Yaqi Wang (Journal of Plant Growth Regulation, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Antimicrobial polyketides from an endophytic fungus Arcopilus aureus HJ-7 from Ardisia mamillata Hance - Li-Qi Liang; Xian-Hua He; Chun-Yan Wei; Jing-Xian Zhao; Qian Wu; Min Liang; Jun Li; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Surfactant-improved microphase separation of perfluorosulfonic acid pervaporation composite membranes for acid concentration - Baiyi Feng; Jingtong Li; Bing Cao; Rui Zhang (Journal of Water Process Engineering, 2026)

Evolution of groundwater nitrate during managed aquifer recharge: Insights from DOM characteristics and stable isotopes - Congchao Xu; Rui Li; Weiwu Hu; Liting Hao; Bowen Shi; Tianyu Zhang; Chuanping Feng; Nan Chen (Journal of Hazardous Materials, 2026)

Measurement, prediction, and interpretation of industrial carbon unlocking efficiency - Shuai Feng; Guiwen Liu; Rui Li; Kaijian Li; Liu Chen; Xu Duan (Environmental Impact Assessment Review, 2026)

A synergistic strategy to overcome temperature and concentration polarization in a joule-heating CNT/PTFE membrane distillation: From membrane preparation to process mathematic simulation - Tiantian Xu; Longji Li; Xiaojia Li; Liang Feng; Siyu Chen; Yang Xu; Yan Li; Zhiqing Luo; Zhirui Chen; Hongyi Li; Rui Wang; Feiyun Sun (Desalination, 2026)

Complete upcycling of iron phosphate slag via ammonium sulfide: Synchronous recovery of phosphorus, Fe7S8/C catalyst, and elemental sulfur - Shaoxiang Yang; Fei Zhang; Yikun Li; Fang Wang; Jiayu Feng; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2026)

The strong quantum confinement effect of CsPbI3 quantum dots assists the subthreshold turn-on of light-emitting diodes - Mingze Liu; Min Lu; Rui Li; Junzhe Feng; Chunru Fan; Fujun Zhang; Xue Bai; Yu Zhang (Chemical Engineering Journal, 2026)

Functionalizing 3D DNA crystals by replacing non-framework strands - Xinyu Feng; Li Xu; Yunhan Zhang; Shuheng Wei; Dongbao Yao; Huichao Chen; Yueye Wang; Yujing Wu; Hui Hou; Xiao Cui; Qian Meng; Yue Gu; et al. (Chemical Engineering Journal, 2026)

Benchmarking zero-shot vision-language models against supervised learning for concurrent metabolic rate and clothing insulation estimation - Rui Li; Haibo Feng (Building and Environment, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

Reduction of regulatory B cells is associated with high-risk clinical stratification in antiphospholipid syndrome patients - Rui Ma; You-yang Wang; Jing-hong Feng; Wen-yi Li; Yan Long (Immunologic Research, 2026)

A new method for planning long-distance trails using wilderness quality mapping and trajectory data: A case study of the Taihang Mountain National Forest Trail in China - Yunmiao Chen; Yue Cao; Zhangqian Ye; Tao Liu; Pei Wang; Yunshuang Feng; Lingyun Liao; Mingyang Lv; Zhicong Zhao; Alan E. Watson; Steve Carver; Changjia Li; et al. (Journal of Environmental Management, 2026)

Explosive PM2.5 growth and health effects during extreme haze in Shanghai, China: Insights from surface and vertical observations - Wenwen Sun; Yang Chen; Shunyao Wang; Shenghua Zhang; Yuxin Zhang; Rui Li; Jialiang Feng; Jianyu Chen; Tiantao Cheng (Journal of Environmental Sciences, 2026)

Ni/Cu-Impregnated Pd membrane reactor for enhanced Water-Gas shift reaction - Peijun Li; Yeqing Ling; Yanling Feng; Duanhao Wang; Tao Li; Rui Xiao (Fuel, 2026)

A general framework for designing and assessing sustainable and diversified cropping systems: Bridging knowledge-driven, model-aided, and participatory approaches - Zhengyuan Liang; Bowen Ma; Rui-Peng Yu; Yuewen Huo; Shingirai Mudare; Feiyu Ying; Long Li; Fusuo Zhang; Wen-Feng Cong (Field Crops Research, 2026)

Probabilistic modeling of microwave thermal damage at rough rock-cement interfaces using a Bayesian-ANN framework - Jia-Le Li; Fuxin Rui; Yanlong Zheng; Gao-Feng Zhao; Kostas Senetakis (Computers and Geotechnics, 2026)

Fabrication of a pH-responsive nanodelivery platform based on ZnO and kasugamycin for synergistic delivery in the efficient and green management of rice bacterial leaf streak - Shaoyang Sun; Xiang Li; Ziyi Wu; Ze Lv; Yingjian Ma; Rui Zhao; Xinyu Guo; Jianguo Feng; Xuemin Wu; Yong Xu (Chemical Engineering Journal, 2026)

Robust oxygen vacancy surfaces induce chemical bonding interfaces of Bi2Sn2O7/Bi2MoO6 S-scheme heterojunction with asymmetric adsorption sites for efficient photocatalytic nitrogen fixation - Yongli Li; Xin Kong; Rui Bao; Liang Liu; Zhenhua Ge; Feng Liu; Hao Cui; Jianhong Yi (Chemical Engineering Journal, 2026)

Soil biogeochemical controls on the distribution of phosphorus fractions in the Qilian Mountains of China’s drylands - Zeng-Ru Wang; Ji-Liang Liu; Feng-Rui Li (Plant and Soil, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

Multi-frequency controlled-source electromagnetic fast forward modeling in general anisotropic media - Hang-rui Shen; Feng Zhou; Zhi-yong Zhang; Yan Li; Hui Chen; Ying-ying Zheng; Hai-long Ye (Applied Geophysics, 2026)

Submicron biochar induces developmental toxicity, oxidative stress, and DNA damage in zebrafish (Danio rerio) - Anying Chen; Bing Wang; Ping Li; Qianwei Feng; Rui Wang (Chemosphere, 2026)

WTAP-mediated m6A modification of PRMT1 regulates cuproptosis to promote anaplastic thyroid carcinoma progression - Guoli Feng; Changju Chen; Yi Luo; Rui Chen; Xinghong Tang; Taolang Li (Tissue and Cell, 2026)

Quorum sensing in Listeria monocytogenes and control strategies for its inhibition in the food industry - Xinyi Pang; Yunting Wang; Zeyin Feng; Rui Xu; Jing Sun; Xiangfei Li; Yingjian Lu; Hyun-Gyun Yuk (International Journal of Food Microbiology, 2026)

Machine learning-enhanced colorimetric and surface-enhanced Raman scattering-based bimodal lateral flow immunoassay for sensitive and simultaneous detection of the residues of lomefloxacin, ofloxacin, and pefloxacin - Minghui Li; Daqi Chen; Yuhuai Guo; Tianxu Li; Wenjie Guo; Rui Feng; Dien Shao; Ziqi Jiang; Ye Li; Jie Zan (Food Chemistry, 2026)

National-scale insights into occurrence, health risks, and potential sources of 1,4-dioxane in drinking water of China - Feng Yang; Lulu Zhang; Xiaodong Hu; Rui Huang; Chunmei Wang; Yubai Chen; Aimin Li; Qing Zhou; Xiuwen Li; Peng Shi (Environmental Pollution, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

Structural characterization and anti-hepatic fibrosis effects of a novel polysaccharide from Astragalus complanatus seeds - Zhi-Fan Zhu; Shu-Yao Wang; Xiao-Feng Liu; Na Liu; Dian-Chao Dong; Yan-Chun Qi; Na Li; Nan Wang; Jin Tan; Chang Jia; Rui-Qing Cai; Xiao-Qiang Li; et al. (Carbohydrate Polymers, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

Spring Arctic sea ice decline exacerbates summer extreme precipitation in central Asia and drought in northeast China - Lingzhi Zhang; Weiliang Qiu; Qianrong Ma; Li Chen; Rui Hu; Zhonghua Qian; Pengcheng Yan; Guolin Feng (Climate Dynamics, 2026)

The correlation between social support and hopelessness among cancer survivors: a meta-analysis - Lu-Ting Shen; Jian-Zeng Lan; Attiq-Ur-Rehman; Wei Li; Meng-Wei Ge; Rui Feng; Kang Zhong; Si-qi Gao; Hong-Lin Chen (Cancer Causes & Control, 2026)

Molecular epidemiology and clinical characteristics of human adenovirus in children in Hangzhou (2022–2023) - Qin-rui Lai; Wei Chen; Guo-feng Yu; Ya-jun Guo; Shi-qiang Shang; Wei Li (Archives of Virology, 2026)

Research progress on triterpenoids in the genus Rubus : a comprehensive review - Xi-Ya Li; Ting-Cai Dong; Yong-Fan Zi; Yan Luo; Yuan Li; Rui-Feng Mei; Le Cai (Natural Product Research, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Corrigendum to “An oxygen-independent therapeutic nanosystem for fighting against hypoxic and antioxidant microenvironment of tumor” [Journal of Photochemistry and Photobiology B: Biology 268 (2025) 113184] - Zixuan Wang; Shuwei Nie; Manru Wang; Huina Niu; Liqi Wei; Zhiqi Yang; Xin Liu; Yining Chen; Yunan Yang; Chunjiang Li; Qin Zhang; Lina Feng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Dynamic loops and active site mediate substrate recognition of Streptomyces phospholipase D and its functional phospholipid synthesis in dairy system - Linxiu Wu; Chenhao Feng; Tiantian Li; Jiale Cao; Huijun Zhao; Shuang Liang; Mengqin Rui; Lu Pan; Rongkang Hu (Food Research International, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Identification and evaluation of odor emissions from a petrochemical production area in China - Yunxia Feng; Jinchan Peng; Yirong Guo; Qingrun Li; Anshan Xiao; Rui Dong; Dewu Ding; Mingjun Li (Atmospheric Pollution Research, 2026)

Vacuolar K⁺ efflux transporter TaTPK1-5D confers low-K⁺ tolerance of ‘Zhengmai 136’ through interaction with TaCIPK23-4D in bread wheat - Yingna Feng; Qianni Wei; Sisi Sun; Hongbing Zhang; Ting Zhou; Rui Cui; Wenxu Li; Yunqi Liu; Yingpeng Hua; Zhengfu Zhou (Theoretical and Applied Genetics, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

High-Resolution Time-Frequency Feature Enhancement of Bowhead Whale Calls Based on Local Maximum Synchronous Extraction of Generalized S-Transforms - Mingchao Zhu; Rui Feng; Xiaofeng Zhang; Pengsheng Li; Binghua Su (Journal of Marine Science and Engineering, 2025)
Bowhead whales (Balaena mysticetus) are an important species in the Arctic ecosystem, but their conservation is challenged by environmental noise from shipping and climate change. Effective monitoring of Bowhead whale vocalizations is essential for their conservation, yet traditional acoustic methods face limitations in detecting weak and non-stationary signals amidst complex background noise. In this study, we propose a novel method, Local Maximum Simultaneous Extraction of Generalized S-Transforms (LMSEGST), to enhance the feature extraction of Bowhead whale calls. The LMSEGST method integrates generalized S-transforms with local maximum extraction, improving time-frequency resolution and noise immunity. We compare the performance of LMSEGST with traditional methods (STFT, GST, and LMSST) using synthetic and real-world datasets. The results show that LMSEGST outperforms the other methods, with a 28.32% reduction in Rayleigh entropy compared to STFT at 5 dB SNR and a 28.24% reduction compared to LMSST at 10 dB SNR. Additionally, LMSEGST maintained higher SNR values, demonstrating superior noise resistance. These findings suggest that LMSEGST offers a more robust solution for acoustic monitoring of Bowhead whales, particularly in noisy, Arctic environments, contributing to more effective conservation strategies for this species.

7,8-Dihydroxyflavone ameliorates bone loss by regulating TRKB/AKT/FOXO3a pathway in a mouse model of alzheimer’s disease - Dong Liu; Xiaoxiong Li; Peng Shi; Wenjuan Hong; Jie Huang; Mingliang Hou; Linqiu Ma; Qirong Liao; Hongyan Yang; Xiaoyan Fu; Huadong Zhou; Jing Lu; et al. (Psychopharmacology, 2025)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Biodegradable film combined with ploughing: An approach to improve the sustainability of rainfed spring maize production - Rui Qian; Luning Du; Wenjing Li; Wei Wang; Yang Zhang; Yujie Gao; Wenjing Feng; Jiaji Ding; Wenbo Lv; Pengyao Qin; Tie Cai; Xiaolong Ren; et al. (Soil and Tillage Research, 2025)

Spatio-temporal variations of soil particle size distribution under wind erosion in a temperate grassland: A seven-year landscape scale revisited analysis - Yuxin Feng; Zhuodong Zhang; Zhuoli Zhou; Bo Chen; Ying Li; Xinyu Zou; Rui Xu; Shuran Gao (Soil and Tillage Research, 2025)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Arrangement optimization of wingsails subject to complex mutual aerodynamic interference: A numerical study - Ranqi Ma; Daize Li; Rui Zhang; Feng Tian; Zhiqiang Tang; Jianlin Cao; Yuhao Xie; Zihan Jing; Jijun Chen; Xiaowu Li; Lianzhong Huang (Ocean Engineering, 2025)

Resilient polyurea barriers for copper smelting wastewater containment: Synergistic effects of microstructural optimization and heavy metal immobilization - Feng Chen; Linhai Ye; Wenchang Li; Rui Xiang; Youcai Zhao; Qifei Huang; Ya Xu (Journal of Cleaner Production, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

Effect of different small molecule sugars/sugar alcohols as sucrose substitutes in osmotic dehydration on the texture and gel properties of strawberry preserves - Ningyue Liu; Liying Niu; Dajing Li; Jialin Feng; Lei Feng; Zhongyuan Zhang; Chunju Liu; Rui Wang (Food Research International, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

The catalyst derived from MoS2 with Fe/Cu dual-active-sites for peroxymonosulfate activation in antibiotic degradation: The role of Fe and Cu co-doping strategy - Wangbo Wang; Rui Yang; Tao Li; Ting Wu; Qiyu Shi; Yizhou Feng; Zhihua Li; Ying Gao; Weihuang Zhu (Chemical Engineering Journal, 2025)

High-yield synthesis of biomass-derived carbon dots for enhanced taraxacum growth - Guanxiong Liu; Hui Wang; Jiaxin Dong; Yinying He; Rui Wang; Xiangli Li; Dongyue Liu; Jing Duan; Jing Feng; Xiaoyu Lu; Lijuan Gui; Sheng Hou; et al. (Biomass and Bioenergy, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Understanding orbital pacing, uplift dynamics, and oceanic influences in aeolian red clay sediments over the Chinese Loess Plateau through cyclostratigraphy insights - Xiaohao Wei; Rui Zhang; Vadim A. Kravchinsky; Joseph V. Ferraro; Jie Qin; Minghao Ma; Dongyue Zhang; Xiaojuan Li; Leping Yue; Jianxing Li; Yong Xu; Ji Ma; et al. (International Geology Review, 2025)

Dynamics of multiple rogue waves for (3+1)-dimensional variable-coefficient potential Yu-Toda-Sasa-Fukuyama equation - Yi-Lin Tian; Wen-Yuan Li; Nong-Sen Li; Rui-Gang Zhang; Ji-Feng Cui (Wave Motion, 2025)

Discovery of ca. 2.33–2.22 Ga magmatic activities in the Longshan Complex bordering the southwestern margin of the North China Craton: Implications for tectonic transformation - Yi-Yi Zhang; Jun-Sheng Lu; Rui-Ying Zhang; Yu-Ting Li; Xu Kong; Gang Liu; Qiang Feng; Zeng-Yin Duan; Juan-Juan Li (Lithos, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

Electrochemical dimerization of furfural and 5-hydroxymethylfurfural into aviation fuel precursors: Optimization and mechanistic insights - Jiahui Chen; Xian Pan; Xinchi Zhang; Xin Zhou; Shiliang Wu; Youn-Sang Bae; Ismagil Shakirovich Khusnutdinov; Feng Gong; Tao Li; Huiyan Zhang; Rui Xiao (Journal of Cleaner Production, 2025)

An intelligent colorimetric paper-based hypoxanthine biosensor enabled by smartphone and dual-enzyme system for efficient shrimp freshness monitoring - Wenhui Dong; Rui Feng; Jiaqi Pang; Kaiyue Wei; Jiao Li; Jianan Sun; Sai Wang; Xiangzhao Mao (Food Chemistry, 2025)

Antifungal activity and application of Neurospora sitophila Y-4 against postharvest Penicillium italicum of Citrus reticulata 'Shiyue Ju' via 3-penten-2-one - Lijun Ling; Fanjin Kong; Yijuan Jiang; Wenyue Zhang; Rongxiu Mo; Rui Yue; Yao Li; Lijun Feng; Yongpeng Zhou (Food Bioscience, 2025)

Agricultural plastic Legacy in river Sediments: Abundance, oxidation, and occurrence characteristics of microplastics across rural China - Ge Ma; Kuangjia Li; Wei Zou; Rui Xin; Xiaohan Zhang; Jiaojiao Feng; Zheng Chen; Yinan Yang; Xiaomeng Lou; Kai Zhang; Fengxia Yang (Environmental Pollution, 2025)

Synergistic coupling of Pd@PtRh nanozyme with NiMn2O4/In2S3 Z-scheme heterojunction for ultrasensitive photoelectrochemical sensing of malathion - Rui-Jin Shao; Ke Yin; Lei Zhao; Yadong Xue; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

Prolonged sepsis triggers abnormal mitochondrial dynamics in the limb muscles and diaphragm - Chao Xiong; Fasheng Guan; Jianguo Feng; Jing Jia; Jumei Zhang; Rui Tu; Jie Li; Jun Zhou; Jianglin Wang; Li Liu (Molecular and Cellular Biochemistry, 2025)

Stream sediment geochemical anomaly identification and mapping in the Xinbo area, northern China: Using a catchment basin approach and the Apriori algorithm - Ming Liang; Panfeng Liu; Rui Tang; Xiaodong Wang; Chao Li; Feng Zhu (Applied Geochemistry, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Implementation of a coupled 4D-LSM and NURBS-DDA approach for TBM disc rock cutting - Xin-Dong Wei; Yi-Feng Chen; Fuxin Rui; Hongsu Ma; Shijin Li; Gao-Feng Zhao (Tunnelling and Underground Space Technology, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Macrophage cytoskeletal and immune responses to photoaged and gastrointestinal-transformed polylactic acid micro/nanoplastics with protein corona - Xuri Wu; Feng Tan; Han Zhang; Liping Huang; Yan Wang; Xin He; Rui Cai; Shumin Li (Journal of Hazardous Materials, 2025)

Airborne bioaerosol transmission in hospital waiting corridor: Characteristic, exposure risk and evaluation of prevention strategies - Zhijian Liu; Duo Cai; Chenxing Hu; Lei Jiang; Yongxin Wang; Lina Hu; Rui Rong; Shiyue Li; Jingwei Liu; Jiajun Feng (Journal of Hazardous Materials, 2025)

Synergistic quorum quenching to the diffusible signal factor and AHLs mediated quorum sensing in Thiothrix controlling filamentous sludge bulking - Rui Liu; Lin Feng; Jie Li; Zhuo-Li Yan; Jian-Hong He; Yue Zhi; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Environmental Chemical Engineering, 2025)

The role of hydrolysis on the fibrillization of walnut protein: Self-assembly behavior, structural characteristics - Chang Li; Rui Chen; Jiangjuan Yuan; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Cascade-targeting hydrogel microspheres with biomimetic nanoparticles enable multifaceted anti-inflammatory and antioxidant defense for osteoarthritis management - Shengli Ma; Yuqiao Sheng; Chaoyang Zhang; Feng Li; Na Wei; Jingjing Xu; Rui Xue (Chemical Engineering Journal, 2025)

Self-healing sodium alginate-PEDOT:PSS conductive hydrogel for accelerated burn wound healing and real-time monitoring - Xinshuo Liu; Feng Chen; Yifan Zhang; Zexiang Zheng; Rui Huang; Jinhuan Tian; Hong Li; Changren Zhou; Shuyun Zhang; Huihua Xu; Lihua Li (Chemical Engineering Journal, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

ROS-responsive hydrogel loaded with berberine liposome protects against intervertebral disc degeneration by inhibiting mitochondrial fission and apoptosis - Cunliang Guo; Lilong Du; Xiaoxun Du; Rui Gao; Xinyi Jiao; Zhenhua Li; Tongxing Zhang; Pingsheng Huang; Chuangnian Zhang; Zujian Feng; Weiwei Wang; Baoshan Xu (Chemical Engineering Journal, 2025)

High-Resolution Magnetic Resonance Imaging Radiomics for Identifying High-Risk Intracranial Plaques - Fang Wu; Hai-Ning Wei; Miao Zhang; Qing-Feng Ma; Rui Li; Jie Lu (Translational Stroke Research, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Antifungal cytochalasans from the co-culture of two endophytic fungi Aspergillus spelaeus and Xylaria sp - Xian-Hua He; Ye-Fang Hu; Hua-Chun Feng; Li-Qi Liang; Lan-Fang Zou; Qian Wu; Min Liang; Jun Li; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2025)

Analysis on Phase Polarity of Mandrel Fiber-Optic Vector Hydrophones Based on Phase Generated Carrier Technique - Yatao Li; Jianfei Wang; Rui Liang; Jingjing Feng; Mo Chen; Jiaze Zhao; Zhou Meng (Journal of Marine Science and Engineering, 2025)
In ocean engineering, the demand for fiber-optic vector hydrophones (FOVHs) is increasing. The performance of a FOVH depends on phase consistency between its pressure and acceleration channels, which should match the acoustic field’s properties. Phase polarity, which refers to the alignment of the output signal with the acoustic field direction, is critical. Incorrect phase polarity during sensor assembly can disrupt phase consistency and invalidate directional measurements. This study investigates phase polarity in mandrel FOVHs that use the Phase Generated Carrier (PGC) technique. We develop a theoretical model combining the PGC algorithm with elastic mechanics to analyze the response of acoustic signals. Our model shows that correct demodulated signal polarity requires a specific physical setup: the pressure sensor’s long arm should be on the inner mandrel and the short arm on the outer, while the accelerometer’s positive axis should follow the vector from the long to its short arm. These results are validated through standing wave tube experiments and lake tests. This research provides practical guidelines for the installation and calibration of FOVHs, ensuring phase consistency in underwater acoustic sensing.

Spatiotemporal patterns of fecal cortisol metabolites in critically endangered wild Alpine musk deer in eastern edge regions of Tibetan Plateau: influencing factors and conservation implications - Jiayi Wu; Xiaoping Lu; Shuo Geng; Liquan Shen; Gong Wang; Rui Liu; Jun Qi; Chunting Feng; Junyi Yang; Zhengxu An; Rongxin Li; Na Qiao; et al. (Biologia, 2025)

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Crustal deformation characteristics and tectonic implications on the northeastern margin of the Tibetan Plateau - MengYa Li; HuaJian Yao; JiKun Feng; XianWei Zeng; GuoFu Luo; ChenXi Wang; Rui Ma (Physics of the Earth and Planetary Interiors, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Unveiling the integrated toxicological effects and underlying mechanisms of bisphenol A and cadmium, two hormesis-type endocrine disruptors, on Chromochloris zofingiensis - Rui Feng; Linyuan Song; Haodong Wang; Shixuan Gong; Yangguo Su; Shudong Zhang; Ning Li; Zhao Zhang (Journal of Hazardous Materials, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Ecological security patterns for coordinating development in frozen soil regions - construction framework by coupling climate change and development objectives - Xiangdong Xu; Xu Yang; Lin Lin; Jingxiao Zhang; Jinggan Shao; Rui Zhi; Tao Feng; Zedong Wang; Yuwen Tang; Junyao Li (Journal of Environmental Management, 2025)

Comparative assessment of thyroid disrupting effects of ethiprole and its metabolites: In silico, in vitro, and in vivo study - Zheyuan Song; Zheng Ma; Xueshan Feng; Rui Huang; Qiong An; Yunrui Pan; Jing Chang; Bin Wan; Huili Wang; Jianzhong Li (Journal of Environmental Sciences, 2025)

Quantitative non-volatile sensometabolome of Longjing tea and discrimination of taste quality by sensory analysis, large-scale quantitative metabolomics and machine learning - Xujiang Shan; Linchi Niu; Qianting Zhang; Zhizhen Fang; Yuning Feng; Rui Liang; Zhenxing Xu; Shan Zhang; Le Chen; Weidong Dai; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

Impacts on structure, lipase-inhibitory activity, and digestive characters of fermented coconut protein with Lactobacillus strains - Yufang Tian; Tao Lin; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Elham Azarpazhooh; Marjan Ajami; Ghahvechi Chaeipeima Masha; Xin Rui; Wei Li (Food Bioscience, 2025)

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

Characterizing apple production in China’s apple planting region: Biophysical simulation and machine learning analysis of quality determinants - Renwei Chen; Jing Wang; Chao You; Rui Bai; Puyu Feng; Yang Li; Gang Zhao; Zhenjiang Qu; Qiuyue Li (European Journal of Agronomy, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

An integrated biorefinery strategy for fractionating high-molecular-weight hemicellulose and uncondensed lignin based on tetrapropylammonium hydroxide system - Rui Tian; Bolang Zhu; Jing Li; Xinyuan Zhang; Baozhong Lü; Jing Bian; Jialong Wen; Zhengjun Shi; Yuetong Kang; Feng Peng (Chemical Engineering Journal, 2025)

Synergistic integration of photoelectron utilization and by-product pathway suppression for microbial production of bacitracin - Rui Bai; Wei Chen; Xudong Zhou; Junpeng Li; Yi He; Yong Xiao; Feng Zhao (Chemical Engineering Journal, 2025)

Anion-tailored solvation clusters in methyl acetate electrolyte: Achieving concurrent low temperature operation and high voltage stability - Jiaxuan Feng; Zhaojun Liu; Rui Yang; Xiaochen Wu; Xiangyu Zhang; Jianwei Qiu; Xinyu Li; Ning Liu; Fei Ding; Pengchao Si (Chemical Engineering Journal, 2025)

A rapid and efficient microenvironment improving hyaluronic acid microneedle dressing for burn wound synergistic treatment - Lin Lei; Wei Li; Jiajia Wang; Qi Liu; Feng Zeng; Yunqiang Xiang; Xinyuan Fu; Rui Tao; Zhangyou Yang (Carbohydrate Polymers, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Waste resources based new sulfur fertilizers can better match crop nutrient requirement - ZhiSong Feng; ZhenYa Lu; QingLin Liu; Walter Carciochi; ZengYuan Li; HaiLong Ma; Rui Liu; MaoHua Yang; ChuHao Liu; WeiFeng Zhang; FuSuo Zhang (Resources, Conservation and Recycling, 2025)

A vision foundation model-based method for large-scale forest disturbance mapping using time series Sentinel-1 SAR data - Yuping Tian; Feng Zhao; Ran Meng; Rui Sun; Yuan Zhang; Yanyan Shen; Bin Wang; Jie Liu; Mingze Li (Remote Sensing of Environment, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Hydrodynamic and geomorphological responses of tidal flats to extreme climate events - Renzhi Li; Ya Ping Wang; Rui Yuan; Ning Zhao; Bixuan Tang; Zhixuan Feng; Bruno Castelle (Journal of Hydrology, 2025)

Life-long impacts of nanoplastics to rice plant (Oryza sativa L.): Decreased grain yield with perturbed metallome and soil microbiome - Hongxin Xie; Xuejia Wang; Liwei Cui; Rui Chen; Rui Zhao; Yang Yu; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2025)

Upcycling of cathode materials from spent lithium-ion batteries cathode materials enabled by deep eutectic solvent - Yanshun Liao; Xianglei Meng; Hongwei Wu; Guang Yang; Xinyao Zhang; Rui Tang; Yali Li; Ni Yang; Yibiao Guan; Yuefeng Su; Feng Wu; Qing Huang (Journal of Environmental Chemical Engineering, 2025)

Identification of potential natural compounds to relieve deoxynivalenol-induced intestinal damage based on bioinformatics and reverse network pharmacology - Rui Li; Kang Feng; Yu Du; Xuebin Fan; Yaqin Zhang; Chenli Wang; Jingdi Zhang; Sheraz Ahmad; Rafique Amna; Ci Liu; Ruiyan Niu; Zilong Sun (Food and Chemical Toxicology, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

Polycomponent metal-organic frameworks of substituent polydispersion hydroxypropyl-β-cyclodextrin as inhalable drug carrier - Xiaojian He; Huipeng Xu; Xiangyu Zhao; Feng Li; Ningning Peng; Jialong Wang; Wenqiang Hua; Feixiang Wang; Guanghong Xu; Rui Yang; Jiwen Zhang; Li Wu (Carbohydrate Polymers, 2025)

Calcium-O-Sr-Nd isotope evidence for the origin of REE-bearing carbonatite from metasomatized lithospheric mantle without recycled carbonate - Xing-Hui Li; Ming-Cai Xie; Kui-Feng Yang; Kan Li; Chun-Ming Han; Hai-Dong She; Gai-Zhong Liang; Xiao-Chun Li; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2025)

Elucidating the anti-aging bioactive compounds and mechanisms of Jingfang Granules formula based on network pharmacology and Caenorhabditis elegans - Rui Zhao; Taili Zhao; Tingting Shi; Chuanjiao Feng; Honghua Li; Ying Xu; Qingqing Zhang; Xin Yin; Jingchun Yao; Guimin Zhang; Xuekui Xia (Biogerontology, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Improving agricultural mulching to reduce environmental footprint and enhance economic profit across China - Huihui Wei; Yifan Yang; Li Zhang; Zutao Ouyang; Matthew Tom Harrison; Ke Liu; Guojun Sun; Gary Y. Gan; Feng-Min Li; Li Dong; Rui Wang; Bo Wang; et al. (Resources, Conservation and Recycling, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Intensified East Asian summer monsoon facilitated the formation of the world's largest Late Miocene Hipparion fossil assemblage - Xiaojuan Li; Wei Li; Rui Zhang; Xiaohao Wei; Zhenwei Feng; Chao Wang; Zhihao Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

An oxygen-independent therapeutic nanosystem for fighting against hypoxic and antioxidant microenvironment of tumor - Zixuan Wang; Shuwei Nie; Manru Wang; Huina Niu; Liqi Wei; Zhiqi Yang; Xin Liu; Yining Chen; Yunan Yang; Chunjiang Li; Qin Zhang; Lina Feng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Potentially toxic elements in sediments of China's Shihe River: Urban-agricultural impact assessment and source apportionment - Kai Zhang; Ge Ma; Zheng Chen; Jilu Wang; Xiaomeng Lou; Yinan Yang; Jiaojiao Feng; Fengxia Yang; Kuangjia Li; Chenxuan Shang; Rui Xin; Xiangmin Zhang (Journal of Contaminant Hydrology, 2025)

Effects of ultrasonic treatment on protein in goat milk: Changes in structure and function and enhancement of heat-sterilized protein function - Yutong Ma; Rui Li; Shan Qian; Sijing Yuan; Qingkun Zeng; Pan Yang; Ling Li; Xianchao Feng; Lin Chen (International Dairy Journal, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

Demand response based battery energy storage systems design and operation optimization - Rui Li; Qingshi Tu; Haibo Feng; Zhengbo Zou (Energy and Buildings, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

The CG MPNs@UFB composite coatings integrating antibacterial with interface anchoring for sustained protection on inanimate surfaces - Yongxin Zheng; Xi Zhou; Rui Li; Xuejiao Wang; Yabin Niu; Lin Chen; Xianchao Feng (Chemical Engineering Journal, 2025)

Multi-level ROS regulation to activate innate and adaptive immune therapies - Ke-Ke Feng; Cheng-Lei Li; Yi-Fan Tu; Shi-Cheng Tian; Rui Xiong; Bai-Sheng Sa; Jing-Wei Shao (Chemical Engineering Journal, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

An integrated colorimetric biosensing platform containing microneedle patches and aptasensor for histamine monitoring in seafood - Wenjing Wang; Rui Feng; Kaiyue Wei; Jiashuo Xu; Wenhui Dong; Jiao Li; Jianan Sun; Sai Wang; Xiangzhao Mao (Journal of Hazardous Materials, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Hydrophobically modified Cu-ZnO-Al2O3 catalyst for CO2 hydrogenation to methanol - Xiuyun Jiang; Jucang Ke; Rui Li; Hao Huang; Zhihao Liu; Haozhe Feng; Qingxiang Ma; Xinhua Gao; Guangbo Liu; Xiaobo Feng; Tian-Sheng Zhao; Noritatsu Tsubaki (Journal of Environmental Chemical Engineering, 2025)

Ground-based MAX-DOAS observations of formaldehyde and glyoxal in Xishuangbanna, China - Yu Zhang; Xingwei Man; Sanbao Zhang; Li Liu; Fanhao Kong; Tao Feng; Rui Liu (Journal of Environmental Sciences, 2025)

Effects of alkali and alkaline earth metals in biomass on co-pyrolysis characteristics and product distribution of coal and biomass - Na Liu; He Huang; Jun Feng; Rui Li; Xueli Huang; Yulong Wu (Fuel, 2025)

Amelioration of Kluyveromyces marxianus GY-8 on high-fat diet-induced obesity and gut microbiota dysbiosis - Nanyu Tang; Xiaogan Zhao; Tao Lin; Yihan Lin; Chang Xu; Kai Ma; Changliang Zhang; Feng Ji; Ghahvechi Chaeipeima Mahsa; Luyao Xiao; Xin Rui; Wei Li (Food Bioscience, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

A hybrid forcasting model of temperature gradient in longitudinal slab tracks on bridge-subgrade transition zones - Feng Li; YiYao Zhang; Rui Zhou; Qingsong Feng; Zaiwei Li; Guowen Yao; Lihai Zhang (Engineering Structures, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Applicability assessment of six drought indices in different maize producing regions of China - Jie Ma; Peijuan Wang; Rui Feng; Yuanda Zhang; Yang Li; Qi Wang; Dingrong Wu; Yuping Ma (Natural Hazards, 2025)

Design, synthesis, and antifungal activity of novel pyrazole carboxamide derivatives containing benzimidazole moiety as potential SDH inhibitors - Fei Jin; Feng Peng; Xiang-Yi Kong; Wen-Rui Li; Jian-Qi Chai; Min Chen; Ai-Min Lu; Chun-Long Yang; Guo-Hua Li (Molecular Diversity, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

Effects of starvation-refeeding on antioxidant status, metabolic function, and adaptive response in the muscle of Cyprinus carpio - Wenrong Feng; Jianlin Li; Yuanfeng Xu; Gang Jiang; Shengyan Su; Zhihua Zhang; Rui Jia; Yongkai Tang (Aquaculture, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Unravelling the inhibition mechanism of 1-octene-3-ol combined with 3-heptene-2-one on Aspergillus flavus and its application in the preservation of wolfberries - Lijun Ling; Rongxiu Mo; Wenyue Zhang; Yijuan Jiang; Fanjin Kong; Lijun Feng; Yao Li; Rui Yue; Yongpeng Zhou (Postharvest Biology and Technology, 2025)

Palynological and geochemical evidence for East Asian monsoon evolution from the northern South China Sea during the middle to late Eocene - Mengtian Gao; Li You; Gaowei Hu; Manuel Chevalier; Xiaohua Teng; Qi Feng; Yabing Chen; Feng Jin; Rui Yang; Jingyu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Antioxidant and immunomodulator nanoengineered probiotics for synergistic therapy of inflammatory bowel disease - Pandi Peng; Rui Ding; Junru Wang; Luofeng Yu; Yuxin Guo; Pengyu Chen; Tao Feng; Peng Li (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

TiO2 nanoparticles improves cadmium toxicity tolerance in Hemerocallis citrina Baroni by modulating photosynthetic and antioxidative profile - Wei Liu; Yuwei Feng; Shuo Chen; Rui Chu; Siyue Li; Yue Wang; Yongqing Yan (Plant Cell Reports, 2025)

Monthly variations of the spring greenness response across boreal Eurasia to the preceding wintertime northern annular mode during 1982–2022 - Jing Li; Weiming Zeng; Ruichen Lin; Zhiqing Xu; Xilin Xie; Feng Su; Rui Zhao; Anmin Duan (Climate Dynamics, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

Identification and characterization of Colletotrichum camelliae, the causal agent of leaf spot of Polygonatum odoratum in China - Rui Zhang; Yiyi Feng; Chun Wu; Ke He; Shaming Fu; Cheng Li (Crop Protection, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Theoretical study on the characteristics of P1 wave seismic scattering induced by seabed slope with local interlayers - Feng Guang-rui; Xie Li-quan (Soil Dynamics and Earthquake Engineering, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Sulfur dioxide increases testosterone biosynthesis by activating ERK1/2 pathway and disrupting autophagy in Leydig cells - Xiang Li; Yan Shi; Sha Liu; Zhiyuan Feng; Haoran Xiao; Rui Li; Zirou Li; Xinyue Zhang; Yongli Han; Jundong Wang; Chen Liang; Jian Bai; et al. (Journal of Hazardous Materials, 2025)

Fruit wines classification enabled by combing machine learning with comprehensive volatiles profiles of GC-TOF/MS and GC-IMS - Changlin Zhou; Yashu Yu; Jingya Ai; Chuan Song; Zhiyong Cui; Quanlong Zhou; Shilong Zhao; Rui Huang; Zonghua Ao; Bowen Peng; Panpan Chen; Xiaoxiao Feng; et al. (Food Research International, 2025)

Spectral analysis of the impact of various polysaccharides on the entrapment of curcumin by whey protein isolate - Yuhan Yan; Rui Tang; Feng Li; Liurong Huang; Yu Chen; Ronghai He (Food Chemistry, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Migration and distribution of thallium related with lead-zinc smelting enterprises from raw materials to soil: In-situ insight using diffusive gradients in thin-films - Wenhao Wang; Siwei Deng; Jiang Yu; Yi Wu; Wenjuan Feng; Qin Fan; Rui Zhou; Peirou Li; Wei Deng; Zhi Huang; Jie Yu; Weiwei Zhu (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Recombinant Human Nerve Growth Factor Integrated Hyaluronic Acid Hydrogel Microneedles for Corneal Nerve Repairing - Ziqing Feng; Rui Liu; Ruoyan Wei; Yunzhe Wang; Tianze Cui; Chang Liu; Xiaojun Hu; Chi Zhang; Bin Kong; Meiyan Li; Xingtao Zhou (Chemical Engineering Journal, 2025)

Computational Design and Optimization of Multi-Compound Multivesicular Liposomes for Co-Delivery of Traditional Chinese Medicine Compounds - Mengjie Rui; Yali Su; Haidan Tang; Yinfeng Li; Naying Fang; Yingying Ge; Qiuqi Feng; Chunlai Feng (AAPS PharmSciTech, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

The improved gel properties of myofibrillar protein under low salt condition by ultrasound-assisted sodium tripolyphosphate - Rui Li; Xiaoqi Li; Chen Wang; Guiming Zhang; Yabin Niu; Fashan Wei; Lin Chen; Xianchao Feng (Meat Science, 2025)

UPLC-HDMS revealed numerous novel compounds in soybean crude oil - Zhaohui Sun; Feng Dong; Rui Zhang; Xinyu Song; Xiaocai Huang; Yingran Dong; Xiaofei Jia; Shunian Luo; Ying Li; Maoqing Wang (Food Chemistry, 2025)

A review of emission characteristics and risk assessments of volatile organic compounds in petrochemical industry areas - Jinchan Peng; Yunxia Feng; Anshan Xiao; Bo Li; Dewu Ding; Guolong Wang; Rui Dong (Environmental Pollution, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

An efficient, high-throughput enrichment system for the rapid detection of E. coli at low concentrations in water - Binghuan He; Fangzhou Zhang; Pengfei Gong; Rui Sun; Jianxin Cheng; Chenghui Jin; Bo Liu; Jianlong Zhao; Shilun Feng; Bei Li (Analytica Chimica Acta, 2025)

Molecular mechanisms behind the inhibitory effects of ginsenoside Rg3 on hepatic fibrosis: a review - Zhao-feng Tian; Rui-yi Hu; Zi Wang; Ya-jun Wang; Wei Li (Archives of Toxicology, 2025)

Grevillosides R-S: glucosides of 5-alkylresorcinol derivatives from roots of Ardisia crispa (Thunb.) A. DC - Xing-xiang Long; Shuang Zhang; Li-juan Xiang; Rui-hang Hu; Ting-ting Feng; Ying Zhou; Xin Yin (Natural Product Research, 2025)

Three new isoquinoline alkaloids from the fermentation of Aspergillus sp. 0338 and their anti-MRSA activities - Min Yang; Miao Dong; Qing-Yang Wu; Shui Yao; Gui Pu; Yue-Yu Ma; Rui-Feng Xiong; Qiu-Fen Hu; Fang Wang; Yin-Ke Li (Natural Product Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Volatile organic compounds from Stenotrophomonas geniculata J-0 as potential biofumigants manage bulb rot caused by Fusarium oxysporum in postharvest Lanzhou lily - Lijun Ling; Rui Yue; Yuanyuan Wang; Lijun Feng; Ling Yang; Yao Li; Rongxiu Mo; Wenyue Zhang; Fanjin Kong; Yijuan Jiang; Yongpeng Zhou (World Journal of Microbiology and Biotechnology, 2025)

H-NS-Mediated Regulation of Swimming Motility and Polar Flagellar Gene Expression in Vibrio parahaemolyticus - Yue Zhou; Jingyang Chang; Feng Li; Mei He; Rui Li; Yaqin Hou; Yiquan Zhang; Renfei Lu; Ming Yang (Current Microbiology, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

Identifying the Pathogenicity of a Novel NPRL3 Missense Mutation Using Personalized Cortical Organoid Model of Focal Cortical Dysplasia - Rongrong Lu; Ying Xu; Hao Li; Man Xiong; Wenhao Zhou; Weijun Feng; Rui Zhao (Journal of Molecular Neuroscience, 2024)

A Method for Aliasing Metal Particle Recognition Based on Three-Coil Sensor Using Frequency Conversion - Di Wu; Yucai Xie; Chenyong Wang; Xian’an Gu; Feng Gu; Guoqing Li; Hongpeng Zhang; Yunsheng An; Rui Li; Changzhi Gu (Journal of Marine Science and Engineering, 2024)
The diesel engine on a ship is crucial as it serves as the primary power source, significantly influencing both the vessel’s efficiency and safety. Monitoring metal wear particles found in lubricating oil is essential for assessing the lubrication condition of mechanical equipment onboard and anticipating potential failures. Analyzing these metal wear particles allows us to gauge the wear status of bearing pairs within the machinery, thereby providing a technical foundation for routine maintenance activities. However, under real operating conditions, it can be challenging to prevent multiple metal particles from simultaneously passing through sensors. To address this issue, this research introduces an innovative three-coil induction sensor that employs a variable-frequency excitation technique to explore how induction and eddy currents interact. The findings indicate that when the excitation frequency changes, the peak value of the signal from 337 μm iron particles only increases by 3.35 times, while the peak value of the signal from 340 μm copper particles increases by 22.69 times. Consequently, this study recommends using changes in excitation frequency to differentiate between mixed metal particles made of various materials.

A highly-efficient peroxymonosulfate activator using a sewage sludge derived biochar supported cobalt oxide: Mechanism and characteristics - Qiyu Shi; Rui Yang; Meiyu Liu; Yizhou Feng; Zhihua Li; Weihuang Zhu (Process Safety and Environmental Protection, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Contribution of alkaline magmas to the petrogenesis of Triassic aluminous A-type granites on Liaodong Peninsula, Northeastern China - Yu-Sheng Zhu; Jin-Hui Yang; Jin-Feng Sun; Jing-Yuan Chen; Lei Xu; Rui Li; Bao-Quan Zhou (Lithos, 2024)

A review of nanoscale MnOx-based materials: Catalytic and oxidative properties for pollutant degradation in multiple mediums - Zi-Chun Lu; Hai-Zhu Liu; Rui Zhang; Bin Li; Jin-Xing Zhou; Hai-Feng Su (Journal of Water Process Engineering, 2024)

Recovery of low-concentration waste acid by electrodialysis: Modeling and validation - Feng-rui Li; Yu-xiang Jia; Meng Wang (Journal of Cleaner Production, 2024)

Calcium alginate-biochar composite immobilized A. ferrooxidans effectively removes sulfate and ferric iron from acid mine drainage - Rui Li; Bing Wang; Bin Gao; Lei Li; Pan Wu; Xueyang Zhang; Miao Chen; Qianwei Feng (Journal of Environmental Management, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

A double-layer film based on the strategy of tannic acid-anthocyanin co-pigmentation and tannic-crosslinked-gelatin/−reduced Ag nanoparticles for beef preservation and monitoring - Rui Li; Haoyu Feng; Shancan Wang; Di Zhuang; Youhong Wen; Jie Zhu (Food Chemistry, 2024)

Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Guan Cheng; Rui Qu; Ge Song; Xing Li; Feng Zhang; Jingxuan Wang; Wenzhu Li; Jiahui Wen; Yanfei Xiao; Yiqiu Wei; Weiqian Zhang; Xiaofang Yi; et al. (Environmental Research, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Increasing cross-border dust storm from Mongolia to China during 1987–2022 - Yihao Ma; Rui Mao; Cuicui Shi; Xingya Feng; Li Ma; Xingyu Song (Global and Planetary Change, 2024)

Regulation of anthocyanin synthesis in red lettuce in plant factory conditions: A review - Hadiqa Anum; Kun Li; Javaria Tabusam; Said Abdelhalim Abdelaty Saleh; Rui-feng Cheng; Yu-xin Tong (Food Chemistry, 2024)

Enhancing electrocatalytic oxidation via spatial confinement in Ti4O7 Nanopore Membranes: Synthesis, Characterization, and Mechanistic insights - Rui Pang; Pingzhou Duan; Mingyue Li; Dan Li; Lixia Zheng; Yifei Zhang; Li Liu; Jian Wei; Feng Qian (Chemical Engineering Journal, 2024)

Zirconium based metal–organic frameworks with aggregation-induced electrochemiluminescence for sensitive analysis of aflatoxin B1 by signal dual-amplification strategy - Yuan Li; Xue Dong; Tingting Wu; Xiaoyue Zhang; Xiang Ren; Rui Feng; Yu Du; Jin Yong Lee; Xuejing Liu; Qin Wei (Chemical Engineering Journal, 2024)

Cost-efficient breakthrough: Fabricating multifunctional woven hydrogels from water-soluble polyvinyl alcohol yarn - Chenxing Xiang; Yuanhao Tian; Huiming Ning; Ning Hu; Lidan Zhang; Feng Liu; Rui Zou; Shu Wang; Jie Wen; Leilei Li (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Sustainable rewritable paper based on photoresponsive tungsten oxide quantum dots for anti-counterfeiting and waterproofing - Tiandi Chen; Xiaoxue Mai; Yiyun Li; Tingting Wang; Rui Gong; Feixiong Chen; Hongjie Huang; Zhiyong Yan; Feng Wang (Chemical Engineering Journal, 2024)

Retrieval and validation of the dawn-dusk land surface temperature from FY-3E MERSI-LL - Yuanliang Cheng; Li Ni; Xiujuan Li; Rui Feng; Hua Wu (International Journal of Remote Sensing, 2024)

Association Between Zinc Ion Concentrations in Seminal Plasma and Sperm Quality: A Chinese Cross-Sectional Study - Gangxin Chen; YeBin Feng; Rui Yang; Haiyan Li; Zhiqin Huang; Zhihao Li; Beihong Zheng; Yan Sun (Biological Trace Element Research, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

Multifunctional Ni-MOF (3D) with N-rich structures for self-generated reactive oxygen species and enhanced electron transfer for synergistic degradation of organic pollutants and removal of Hg(II) - Si-Han Zhou; Rui-Dong Wang; Yun Yang; Hui-ying Li; Li-jun Luo; Feng-zhi Jiang (Journal of Cleaner Production, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Polydopamine-assisted minute fabrication of vertically aligned ZIF-L membranes for CO2/N2 separations - Keming Zhang; Sihui Li; Xiaohe Tian; Rui Zhang; Xiaoting Feng; Qingnan Wang; Yanting Tang; Chenlu Liu; Hongxia Gao; Shaofei Wang (Chemical Engineering Journal, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Rich-silicon rice husk ash increases iron plaque formation and decreases cadmium and arsenic accumulation in rice seedlings - Jiao-Feng Gu; Xuan-Tao Yi; Kun Ouyang; Qian Li; Ping You; Rui Zhou; Peng Zeng; Ye Liao; Hang Zhou (Chemosphere, 2024)

Bifunctional materials based on poly(3-aminocarbazole) for efficient and highly selective detection and adsorption of Hg2+ in water - Dongkui Zhang; Feng Xu; Jianing Li; Rui Zhang; Jiangbin Xia (Chemosphere, 2024)

Water and fertilizer decision model for synergistic optimization of yield, quality and efficiency of cherry tomato based on combination evaluation - Rui Li; Jiaming Bai; Dayong Li; Xinru Ren; Daiwei He; Rongcheng Du; Ziqi Feng; Zhi Zhang (Computers and Electronics in Agriculture, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Constructing Ni/ZnMOx composite metal oxide adsorbents with excellent desulfurization capacity and thermal stability for reactive adsorption desulfurization - Pu Dai; Mengya Guo; Hui Ge; Caimei Fan; Xuekuan Li; Xiuquan Liu; Junpeng Feng; Rui Li; Mingxing Tang (Fuel, 2024)

Decoding polyphenol metabolism in patients with Crohn’s disease: Insights from diet, gut microbiota, and metabolites - Liyuan Xiang; Shuyu Zhuo; Wanrong Luo; Chunyang Tian; Shu Xu; Xiaozhi Li; Yijun Zhu; Rui Feng; Minhu Chen (Food Research International, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Mechanical performance analysis of double-block ballastless tracks in intercity railways under temperature and train loads - Rui Zhou; Hongzhang Yin; Yang Li; Yinggang Tao; Qingsong Feng; Lihai Zhang (Engineering Structures, 2024)

Transport behavior of particles and evolution of plugging zones in rough fractures: Insights from a novel coupled CFD-DEM model - Xu Yang; Jiaxin Feng; Gao Li; Rui Li; Ze Li; Hongtao Li (Computers and Geotechnics, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Design and synthesis of ligustrazine derivatives as potential anti-Alzheimer’s agents - Xu-fei Chen; Shan-shan Li; Yu-jun Bai; Ze-feng Zhao; Ya-jun Bai; Gu Gong; Xi-rui He; Xiao-hui Zheng (Natural Product Research, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Gas chromatography-mass spectrometry and non-targeted metabolomics analysis reveals the flavor and nutritional metabolic differences of cow's milk fermented by Lactiplantibacillus plantarum with different phenotypic - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2024)

Lung microbiota participated in fibrous microplastics (MPs) aggravating OVA-induced asthma disease in mice - Qian Wu; Rui Li; Yifei You; Wei Cheng; Yan Li; Yan Feng; Yuqin Fan; Yan Wang (Food and Chemical Toxicology, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Research Overview on Sugarcane Deep Processing and Comprehensive Utilization in China - Gan-Lin Chen; Jing Chen; Bo Lin; Ling-Zhi Zhao; Feng-Jin Zheng; Krishan K. Verma; Yang-Rui Li (Sugar Tech, 2024)

Wogonin preconditioning of MSCs improved their therapeutic efficiency for colitis through promoting glycolysis - Mengye Wu; Cuiping Li; Xue Zhou; Zhiyong Wu; Jianqi Feng; Xiaolu Guo; Rui Fang; Qinghai Lian; Ming Pan; Xiaorong Lai; Yanwen Peng (Inflammopharmacology, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Association Between Multiple Metal(loid)s Exposure and Blood Lipid Levels: Evidence from a Cross-Sectional Study of Southeastern China - Guihua Du; Xiaoguang Song; Fankun Zhou; Lu Ouyang; Qi Li; Shiying Ruan; Rui Su; Shaoqi Rao; Yanhui Zhu; Jie Xie; Chang Feng; Guangqin Fan (Biological Trace Element Research, 2024)

Impact of high-altitude environments on the motion and settling characteristics of wet-mix shotcrete dust in tunnels - Guoliang Zhang; Zhongan Jiang; Xiaocuan Li; Ya Chen; Bin Yang; Mingli Si; Rui Feng; Ming Wang (Tunnelling and Underground Space Technology, 2024)

Populus euphratica R2R3-MYB transcription factor RAX2 binds ANN1 promoter to increase cadmium enrichment in Arabidopsis - Caixia Yan; Bing Feng; Ziyan Zhao; Ying Zhang; Kexin Yin; Yi Liu; Xiaomeng Zhang; Jian Liu; Jing Li; Rui Zhao; Nan Zhao; Xiaoyang Zhou; et al. (Plant Science, 2024)

A colorimetry-enhanced tri-functional film with high stability by polyphenol-anthocyanin co-pigmentation/conjugate: New prospect for active intelligent food packaging - Rui Li; Haoyu Feng; Shancan Wang; Di Zhuang; Jie Zhu (Food Chemistry, 2024)

Toxic Metal Soil Speciation, Corn Accumulation and Health Risk Assessment in Acidic red soil Farmland in Mineral Industry Area - Yu Qian; Xiaoqi Li; Jie Yang; Rui Zhou; Zijin Hong; Change Liu; Shiyu Li; Yonggui Zhao; Denggao Fu; Ying Pan; Huan Feng; Marek Kolenčík; et al. (Water, Air, & Soil Pollution, 2024)

Cytokines-activated nuclear IKKα-FAT10 pathway induces breast cancer tamoxifen-resistance - Xueyan Chen; Weilin Wu; Ji-Hak Jeong; Matjaz Rokavec; Rui Wei; Shaolong Feng; Werner Schroth; Hiltrud Brauch; Shangwei Zhong; Jun-Li Luo (Science China Life Sciences, 2024)

Tracing the impacts of ecological water replenishment on the sources and transformation of groundwater nitrate through isotope and microbial analysis - Congchao Xu; Bowen Shi; Zihao Jia; Di Liu; Weiwu Hu; Chuanping Feng; Rui Li (Science of The Total Environment, 2024)

Culturing the uncultured marine fungi in the omics age: Opportunities and challenges - Zhi-Feng Zhang; Fang Liu; Li-Rui Liu; Meng Li; Lei Cai; Shuangping Liu; Jian Mao (Fungal Biology Reviews, 2024)

High-pressure microfluidization enhanced the stability of sodium caseinate-EGCG complex-stabilized fish oil emulsion - Wei Tang; Rui Wang; Minghui Li; Qingchun Zhang; Jianfei He; Dan Liu; Yuqi Feng; Weilin Liu; Jianhua Liu (Food Chemistry, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Variations in antibiotic resistomes associated with archaeal, bacterial, and viral communities affected by integrated rice-fish farming in the paddy field ecosystem - Yiran Hou; Weixu Diao; Rui Jia; Wei Sun; Wenrong Feng; Bing Li; Jian Zhu (Environmental Research, 2024)

High-spatial resolution ground-level ozone in Yunnan, China: A spatiotemporal estimation based on comparative analyses of machine learning models - Xingwei Man; Rui Liu; Yu Zhang; Weiqiang Yu; Fanhao Kong; Li Liu; Yan Luo; Tao Feng (Environmental Research, 2024)

Efficient acidic CO2 electroreduction to formic acid by modulating electrode structure at industrial-level current - Zhenhui Wang; Hongdong Li; Tian Dong; Yanling Geng; Xiaofeng Tian; Rui Chang; Jianping Lai; Shouhua Feng; Lei Wang (Chemical Engineering Journal, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

Loss in the rare bacterial diversity drives the monocropping obstacle of cut chrysanthemum - Jun Li; Feng Meng; Niannian Chen; Maibo Jiang; Guixin Chu; Rui Tao (Journal of Soil Science and Plant Nutrition, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

Variations in Column Concentration of Greenhouse Gases in China and Their Response to the 2015–2016 El Niño Event - Ningwei Liu; Lingjun Xia; Youjun Dou; Shaorou Dong; Jing Wen; Ying Wang; Rui Feng; Ruonan Wang; Yuhe Li (Journal of Meteorological Research, 2024)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Two new cytochalasins from the endophytic fungus Xylaria sp. GDGJ-77B - Zhao-Long Xu; Ben-Chao Li; Li-Li Huang; Liu-Xia Lv; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Fossil woods of Cryptocarya (Lauraceae) from the middle Miocene of Southwest China - Rui Zhang; Lu-Liang Huang; Shu-Feng Li; Tao Su; Alexei A. Oskolski (Review of Palaeobotany and Palynology, 2024)

Early Cretaceous intrusive rocks in the Gangdese arc of southern Tibet do not support shallow subduction of the Neo-Tethyan oceanic lithosphere - Feng Wang; Qing Wang; Di-Cheng Zhu; Shi-Min Li; Peter A. Cawood; Rui-Qiang Wang; Jian-Kang Yi; Liang-Liang Zhang; Jin-Cheng Xie (Lithos, 2024)

Comprehensive utilization for hydrothermal conversion products of food waste - Rui Bao; Shuzhong Wang; Jiaqi Feng; Kai Liu; Hui Liu; Fan Zhang; Yuanwang Duan; Zicheng Li; Jianqiao Yang (Journal of Cleaner Production, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Current advances in porous organic nanoplatforms for tumor theranostics - Wanhao Qi; Bin Liu; Yian Li; Zhu Liu; Shiqiao Rui; Shuaipeng Feng; Junya Lu; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Enhancing nitrogen removal efficiency for anammox granular sludge at low temperature by fulvic acids from different sources - Li-Li Qiao; Yun-Rui Feng; Shao-Yang Liu; Peng Yan (Journal of Water Process Engineering, 2024)

Constructing of Fe-Cu bimetallic MOFs derived electro-Fenton cathode for efficient norfloxacin removal - Yixin Du; Zhenpeng Li; Rui Feng; Qing Liu; Yanming Yang; Meng Sun; Yanxia Zhao; Tao Yan; Liangguo Yan (Journal of Environmental Chemical Engineering, 2024)

Endophytic Stenotrophomonas geniculata KJ-6 via producing antifungal volatile organic compounds effectively control Lanzhou lily postharvest diseases - Lijun Ling; Yuanyuan Wang; Jialin Li; Wenting Cheng; Rui Yue; Lijun Feng; Yao Li; Yongpeng Zhou; Lu Lu (Food Bioscience, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Transcriptomic analysis of hydrogen peroxide-induced liver dysfunction in Cyprinus carpio: Insights into protein synthesis and metabolism - Wenrong Feng; Yuanfeng Xu; Shengyan Su; Fan Yu; Jianlin Li; Rui Jia; Changyou Song; Hongxia Li; Pao Xu; Yongkai Tang (Science of The Total Environment, 2024)

Deciphering the biotic and abiotic drivers of coalescence asymmetry between soil and manure microbiomes - Chunkai Li; Xianping Li; Sana Romdhane; Yanhong Cheng; Gen Li; Rui Cao; Peng Li; Jingjing Xu; Yexin Zhao; Yang Yang; Jiaguo Jiao; Feng Hu; et al. (Science of The Total Environment, 2024)

In situ membrane separation drives nitrous oxide enrichment from nitrate denitrification for energy recovery - Yong-Tao Lv; Yue Li; Yixin Wang; Xiaolin Chen; Rui Miao; XuDong Wang; Chengjie Feng; Lei Wang (Journal of Water Process Engineering, 2024)

Removal of sulfonamide antibiotics by non-free radical dominated peroxymonosulfate oxidation catalyzed by cobalt-doped sulfur-containing biochar from sludge - Chen Wang; Yuanyuan Li; Yukun Wang; Yan Zhang; Jingbo Feng; Xiaomeng An; Rui Wang; Yinyin Xu; Xiuwen Cheng (Journal of Hazardous Materials, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Occurrence, distribution and ecological risk assessment of herbicide residues in cropland soils from the Mollisols region of Northeast China - Rui Li; Wenyou Hu; Hanqiang Liu; Biao Huang; Zhongjun Jia; Feng Liu; Yuguo Zhao; Khalid Saifullah Khan (Journal of Hazardous Materials, 2024)

Coevolution mechanisms of stakeholder strategies in the green building technologies innovation ecosystem: An evolutionary game theory perspective - Rui Zhao; Li Peng; Yanling Zhao; Yingbin Feng (Environmental Impact Assessment Review, 2024)

Study on the influence of perforation parameters on hydraulic fracture initiation and propagation based on CDEM - Jing Li; Lixiang Wang; Chun Feng; Rui Zhang; Xinguang Zhu; Yiming Zhang (Computers and Geotechnics, 2024)

ZIF-8 Gel/PIM-1 mixed matrix membranes for enhanced H2/CH4 separations - Keming Zhang; Xianye Luo; Sihui Li; Xiaohe Tian; Qingnan Wang; Chenlu Liu; Yanting Tang; Xiaoting Feng; Rui Zhang; Shuangfeng Yin; Shaofei Wang (Chemical Engineering Journal, 2024)

An efficient synthesis and organic-modification coupling strategy to produce highly dispersed ultrathin antioxidant intercalated layered double hydroxides for enhancing performance of polypropylene composites - Zijia Li; Menghua Zhao; Rui Tian; Yalin Shi; Weiliang Tian; Yiqing Bai; Meng Xu; Kai Xu; Dali Gao; Yongjun Feng (Chemical Engineering Journal, 2024)

Biochar loaded with ferrihydrite and Bacillus pseudomycoides enhances remediation of co-existed Cd(II) and As(III) in solution - Rui Cao; Guodong Kang; Weiwen Zhang; Jihai Zhou; Wangliang Xie; Zhenzhen Liu; Li Xu; Feng Hu; Zhen Li; Huixin Li (Bioresource Technology, 2024)

Summer electricity consumption and its drivers in urban areas - Feng Gao; Zhenzhi Jiao; Shunyi Liao; Rui Liu; Zhisai Hu; Yang Liu; Hongbao Li; Wangyang Chen; Xin Chen; Guanyao Li (Applied Geography, 2024)

An AI-powered approach to improving tunnel blast performance considering geological conditions - Yaosheng Liu; Ang Li; Feng Dai; Ruochen Jiang; Yi Liu; Rui Chen (Tunnelling and Underground Space Technology, 2024)

Failure mechanism of rock masses with complex geological conditions in a large underground cavern: A case study - Jin-Shuai Zhao; Shu-Qian Duan; Bing-Rui Chen; Lei Li; Ben-Guo He; Peng-Xiang Li; Guo-Feng Liu (Soil Dynamics and Earthquake Engineering, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Investigation of the intrinsic characteristics of two lock-in regions in a 10:1 π-shaped deck - Jiaying Wang; Feng Wang; Rui He; Jiawu Li; Jianming Hao; Jiupeng Zhang; Xiaoming Huang (Ocean Engineering, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Dispersion of sandy sediments during marine–continental transition: An integrated study from the Late Paleozoic western Ordos Basin - Zhiwei Wang; Lei Liu; Jianling Hu; Feng Wang; Dan Li; Jingqi Zhang; Shuyue Zhu; Rui Zhang; Fei Zhao; Chenggong Zhang; Siyi Fu; Hongde Chen (Marine and Petroleum Geology, 2024)

Screening the phytotoxicity of micro/nanoplastics through non-targeted metallomics with synchrotron radiation X-ray fluorescence and deep learning: Taking micro/nano polyethylene terephthalate as an example - Hongxin Xie; Chaojie Wei; Wei Wang; Rui Chen; Liwei Cui; Liming Wang; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2024)

China's anthropogenic N2O emissions with analysis of economic costs and social benefits from reductions in 2022 - Rui Feng; Zhenhua Li; Zhuangzhou Qi (Journal of Environmental Management, 2024)

Characteristics, sources, and health risk assessment of atmospheric particulate mercury in Guanzhong Basin - Xiaofei Li; Rui Zhang; Lekhendra Tripathee; Feng Yu; Jingning Guo; Wen Yang; Junming Guo; Shichang Kang; Junji Cao (Environmental Pollution, 2024)

The occurrence of pollutants in organisms and water of inland mariculture systems: Shrimp aquaculture is a procession of Microplastics accumulation - Kexin Song; Siqi Xie; Changwen Li; Jincheng He; Wei Jin; Rui Wang; Wei Huang; Pingjing Li; Zhihua Feng (Environmental Pollution, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Cycloaspeptide H, a cyclopentapeptide from the endophytic fungus Penicillium virgatum - Ben-Chao Li; Liu-Xia Lv; Li-Li Huang; Jia-Tong Zhou; Xi-Shan Huang; Jun Li; Rui-Yun Yang; Wei-Feng Xu (Natural Product Research, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Polysulfide regulation by defect-modulated Ta3N5− electrocatalyst toward superior room-temperature sodium-sulfur batteries - Zhen Zhang; Dan Luo; Jun Chen; Chuyin Ma; Matthew Li; Haoze Zhang; Renfei Feng; Rui Gao; Haozhen Dou; Aiping Yu; Xin Wang; Zhongwei Chen (Science Bulletin, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Natural terpene-based derivatives to control postharvest sclerotinia rot and the involved potential mechanism - Jiuhui Ye; Xin Liu; Rui Zhou; Tuoping Hui; Jian Li; Juntao Feng; Zhiqing Ma; Yanqing Gao (International Journal of Food Microbiology, 2024)

Landscape differentiation of soil bacteria and bacteria-soil-vegetation interactions in desert-oasis ecosystems - Lijuan Chen; Changsheng Li; Zhishan Zhang; Qi Feng; Haiyang Xi; Rui Guo; Chengqi Zhang; Yuxi Wei (Global and Planetary Change, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Effects of Lacticaseibacillus paracasei SNB-derived postbiotic components on intestinal barrier dysfunction and composition of gut microbiota - Luyao Xiao; Changliang Zhang; Xueliang Zhang; Xiaogan Zhao; Ghahvechi Chaeipeima Mahsa; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Research International, 2024)

An intelligent chitosan/gelatin film via improving the anthocyanin-induced color recognition accuracy for beef sub-freshness differentiation monitoring - Rui Li; Shancan Wang; Haoyu Feng; Di Zhuang; Jie Zhu (Food Hydrocolloids, 2024)

The Rpf107 gene, a homolog of LOR, is required for the symbiotic nodulation of Robinia pseudoacacia - Yuanli Li; Yuanyuan Wu; Ziyi Yang; Rui Shi; Lu Zhang; Zhao Feng; Gehong Wei; Minxia Chou (Planta, 2024)

Estimating the complete in-situ stress tensor along deep tunnels with frequent rockbursts near a steep valley - Ben-Guo He; Hong-Pu Li; Xia-Ting Feng; Xiang-Rui Meng (Bulletin of Engineering Geology and the Environment, 2024)

RLP system: A single-tube two-step approach with dual amplification cascades for rapid identification of EGFR T790M - Tao Huang; Yanxi Han; Yuqing Chen; Zhenli Diao; Yu Ma; Lei Feng; Duo Wang; Rui Zhang; Jinming Li (Analytica Chimica Acta, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

O2 plasma-modified carbon nanotube for sulfamethoxazole degradation via peroxymonosulfate activation: Synergism of radical and non-radical pathways boosting water decontamination and detoxification - Shiqi Liu; Zichen Zhang; Rui Lu; Yuankun Mao; Huiru Ge; Can Liu; Chenxi Tian; Siyuan Yin; Li Feng; Yongze Liu; Chao Chen; Liqiu Zhang (Chemosphere, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Moderate selenium alleviates the pulmonary function impairment induced by cadmium and lead in adults: A population-based study - Heze Fan; Ying Xiong; Yuzhi Huang; Lijun Wang; Chenbo Xu; Wenyuan Li; Xueying Feng; Yuxuan Yang; Rui Hua; Zihao Wang; Zuyi Yuan; Juan Zhou (Science of The Total Environment, 2023)

Accelerated aging of lithium-ion batteries: bridging battery aging analysis and operational lifetime prediction - Rui Li; Liying Bao; Lai Chen; Cheng Zha; Jingyang Dong; Nan Qi; Rui Tang; Yun Lu; Meng Wang; Rong Huang; Kang Yan; Yuefeng Su; et al. (Science Bulletin, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Volatile organic compounds of Bacillus spp. as an emerging antifungal resource play a significant role in fruit postharvest disease control - Lijun Ling; Yao Li; Kunling Jiang; Yuanyuan Wang; Hong Luo; Wenting Cheng; Mingmei Pang; Lijun Feng; Rui Yue; Yongpeng Zhou (Food Bioscience, 2023)

Physicochemical stability of lichenan (Usnea longissima) decorated-selenium nanoparticles for cancer chemoprevention - Ziying Yang; Yajie Hu; Panpan Yue; Rui Tian; Huiling Li; Baozhong Lü; Gegu Chen; Feng Peng (Food Bioscience, 2023)

The interaction among Kluyveromyces marxianus G-Y4, Lacticaseibacillus paracasei GL1, and Lactobacillus helveticus SNA12 and signaling molecule AI-2 participate in the formation of biofilm - Xiaomeng Wang; Kai Ma; Changliang Zhang; Feng Ji; Lili Chen; Xueliang Zhang; Ghahvechi Chaeipeima Mahsa; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Microbiology, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Current investigations on global N2O emissions and reductions: Prospect and outlook - Rui Feng; Zhenhua Li (Environmental Pollution, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Volatile organic compounds during routine production and planned shutdown of a petrochemical refinery: Emission characteristics, source and risk assessment - Yunxia Feng; Guolong Wang; Rui Dong; Bo Li; Dewu Ding; Jinchan Peng; Anshan Xiao (Atmospheric Pollution Research, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Effects of root rot on microbial communities associated with goji berry (Lycium barbarum) in the Qaidam Basin, China - Zhilin Feng; Yuancan Xiao; Na Li; Qingbo Gao; Jiuli Wang; Shi-long Chen; Rui Xing (European Journal of Plant Pathology, 2023)

Telluribacter roseus sp. nov., Isolated from the Kumtag Desert Soil - Chu-Ying Feng; Jia-Rui Han; Chun-Yan Lu; Li Gu; Shuai Li; Wen-Hui Lian; Lei Dong; Wen-Jun Li (Current Microbiology, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

A single-site porphyrin (Cu)-based COF electrocatalyst for the electrochemical detection of gallic acid sensitively - Mei-Jie Wei; Jing Li; Ze-Qi Wei; Sheng-Feng Zhang; Zhong-Xia Wang; Heng-Ye Li; Rui Zhang; Fen-Ying Kong; Wei Wang (Analytica Chimica Acta, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Insights into brain perceptions of the different taste qualities and hedonic valence of food via scalp electroencephalogram - Tianyi Yang; Peng Zhang; Lidong Xing; Jin Hu; Rui Feng; Junjie Zhong; Weitao Li; Yizhi Zhang; Qiaoqiao Zhu; Yamin Yang; Fan Gao; Zhiyu Qian (Food Research International, 2023)

Synergetic effect on fouling alleviating of membrane distillation in urine resource recovery by thermally activated peroxydisulfate pretreatment - Yaping Lyu; Xiuwei Ao; Zongsu Wei; Shikun Cheng; Xiaoqin Zhou; Nana Liu; Xuemei Wang; Rui Feng; Zifu Li (Environmental Research, 2023)

Emissions and mitigation potential of endocrine disruptors during outdoor exercise: Fate, transport, and implications for human health - Rui Luo; Tao Zhang; Li Wang; Yong Feng (Environmental Research, 2023)

Insights into simultaneous adsorption of orthophosphate (PO43−) and 1-hydroxyethane 1,1-diphosphonic acid (HEDP) by kaolin/lanthanum carbonate composites: Experimental analysis and DFT calculations - Jun Wan; Rui Li; Xiaonan Feng; Jiazhi Yang; Yuxuan Ye; Sifeng Jian; Xiaowei Zhang (Chemical Engineering Journal, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Symbiotic hemolymph bacteria reduce hexavalent chromium to protect the host from chromium toxicity in Procambarus clarkii - Cheng-Ming Yin; Rui-Geng Niu; Hui Wang; Xian-Yao Li; Qi-Fan Zeng; Jiang-Feng Lan (Journal of Hazardous Materials, 2023)

Zero-valent cobalt and oxygen vacancy rich catalyst derived from Ni/Co metal-organic framework nanosheets for enhanced oxidation of aqueous contaminants via peroxymonosulfate activation - Haodong Hu; Xinlong Yan; Qingxun Hu; Xiaoyan Hu; Rui Feng; Tianbo Li; Wei Zhou; Liping Wang (Journal of Environmental Chemical Engineering, 2023)

Simultaneous detection of heterocyclic aromatic amines and acrylamide in thermally processed foods by magnetic solid-phase extraction combined with HPLC-MS/MS based on cysteine-functionalized covalent organic frameworks - Yanmei Feng; Yiheng Shi; Rui Huang; Panpan Wang; Guoliang Li (Food Chemistry, 2023)

Effects of Lactiplantibacillus plantarum with different phenotypic features on the nutrition, flavor, gel properties, and digestion of fermented soymilk - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Suying Wang; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2023)

The mixed-order chlorine decay model with an analytical solution and corresponding trihalomethane generation model in drinking water - Weinan Feng; Wencheng Ma; Qijia Zhao; Feiyu Li; Dan Zhong; Liming Deng; Yisong Zhu; Zhaopeng Li; Ziyi Zhou; Rui Wu; Luming Liu; Jun Ma (Environmental Pollution, 2023)

Polyamide/UiO-66-NH2 nanocomposite membranes by polyphenol interfacial engineering for molybdenum(VI) removal - Zhenwei Wu; Jianxian Zeng; Zhengqiu Yuan; Rui Zhang; Xiaoping Huang; Fan Feng; Minjuan Chen; Kai Jin; Shengkai Yang; Yahong Li (Desalination, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

The function of steroid terminal monooxygenase in cholesterol or phytosterol degradation by the Mycobacterium neoaurum NRRL B-3805 - Xuemei Li; Rui Zhang; Jianjiong Li; Jinhui Feng; Qiaqing Wu; Dunming Zhu; Yanhe Ma (Systems Microbiology and Biomanufacturing, 2023)

Realgar-Induced Neurotoxicity: Crosstalk Between the Autophagic Flux and the p62-NRF2 Feedback Loop Mediates p62 Accumulation to Promote Apoptosis - Rui Feng; Jieyu Liu; Zhao Yang; Tiantian Yao; Ping Ye; Xiuhan Li; Jiaxin Zhang; Hong Jiang (Molecular Neurobiology, 2023)

Effects of ferrous sulfate modification on the fate of phosphorous in sewage sludge biochar and its releasing mechanisms in heavy metal contaminated soils - Aikelaimu Aihemaiti; Shuoyang Liang; Yingying Cai; Rui Li; Feng Yan; Zuotai Zhang (Environmental Science and Pollution Research, 2023)

Preliminary horizontal co-seismic displacements caused by the 2023 Mw 7.8 and Mw 7.5 Türkiye earthquakes estimated using high-rate GPS observations - Feng Shengtao; Li Jie; Li Guirong; Li Rui; Sulitan Yusan; Aerdake Kadeerbieke (Acta Geophysica, 2023)

Spatiotemporal variations and dominated environmental parameters of nitrous oxide (N2O) concentrations from cascade reservoirs in southwest China - Chiquan He; Rui Qi; Haiyue Feng; Zhenzhen Zhao; Fushun Wang; Daoyuan Wang; Feifei Wang; Xueping Chen; Pu Zhang; Siliang Li; Yuanbi Yi (Environmental Science and Pollution Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

The Dynamics of Dopamine D2 Receptor-Expressing Striatal Neurons and the Downstream Circuit Underlying L-Dopa-Induced Dyskinesia in Rats - Kuncheng Liu; Miaomiao Song; Shasha Gao; Lu Yao; Li Zhang; Jie Feng; Ling Wang; Rui Gao; Yong Wang (Neuroscience Bulletin, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

Prediction of landslide block movement based on Kalman filtering data assimilation method - Yong Liu; Qing-jie Xu; Xing-rui Li; Ling-feng Yang; Hong Xu (Journal of Mountain Science, 2023)

Corrigendum to “Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char” [J. Hazard. Mater. 447 (2023) 130772] - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Emission factors of ozone-depleting chloromethanes during production processes based on field measurements surrounding a typical chloromethane plant in China - Bowei Li; Xingchen Zhao; Xinhe Li; Xiaoyi Hu; Liting Hu; Di Chen; Minde An; Yang Yang; Rui Feng; Liya Guo; Pengnan Jiang; Bo Yao; et al. (Journal of Cleaner Production, 2023)

Novel “all-in-one” multifunctional gelatin-based film for beef freshness maintaining and monitoring - Rui Li; Di Zhuang; Haoyu Feng; Shancan Wang; Jie Zhu (Food Chemistry, 2023)

Assessing the occurrence and sources of synthetic additive pollutants in lake sediments using fecal and sewage markers - Rui Du; Xiaoxia Feng; Pu Wang; Ruiqiang Yang; Gang Li; Jianjie Fu; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Effects of long-term warming on soil prokaryotic communities in shrub and alpine meadows on the eastern edge of the Qinghai-Tibetan Plateau - Wei Li; Lingchen Yuan; Xianli Lan; Rui Shi; Dongdong Chen; Defeng Feng; Xinquan Zhao; Huai Chen (Applied Soil Ecology, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Mechanism for regulation of a forward osmosis membrane by the SA/UiO-66-NH2 composite interlayer and the resulting lithium ion concentration performance - Miaolu He; Yushuang Li; Leihao Feng; Jiaqi Wang; Ze Liu; Lei Wang; Jin Wang; Rui Miao; Xudong Wang (Journal of Cleaner Production, 2023)

Formation and preservation of ultra-deep liquid petroleum in the Ordovician sedimentary succession in Tarim Basin during the neotectonic phase - Feng Li; Xiuxiang Lü; Guangyou Zhu; Jianfa Chen; Rui Wang; Zhenghui Wu; Tao He; Nan Xue (Journal of Asian Earth Sciences, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Insights into dissolved organics in non-urban areas - Optical properties and sources - Feng Yu; Xiaofei Li; Rui Zhang; Jingning Guo; Wen Yang; Lekhendra Tripathee; Lang Liu; Yuqin Wang; Shichang Kang; Junji Cao (Environmental Pollution, 2023)

Revealing the role of calcium alginate-biochar composite for simultaneous removing SO42− and Fe3+ in AMD: Adsorption mechanisms and application effects - Rui Li; Bing Wang; Pan Wu; Jian Zhang; Xueyang Zhang; Miao Chen; Xingxing Cao; Qianwei Feng (Environmental Pollution, 2023)

Structural characterization of a pectic polysaccharide from laoshan green tea and its inhibitory effects on the production of NO, TNF- α and IL-6 - Fan Liu; Rongshen Wang; Ying Chen; Rui Geng; Hong Gao; Feng Wang; Xiaoxiao Liu; Wanzhong Li (Natural Product Research, 2023)

Toxicity and synergistic effect of secondary metabolites isolated from the endophytic fungus LS-Y-1 of Rhododendron przewalskii against Tribolium castaneum - Junyu Liang; Haoshu Wu; Xudong Wang; Rui Feng; Peiyu Lu; Jie Xu; Weibao Kong; Yuan Li (South African Journal of Botany, 2023)

Differential effects of petroleum-based and bio-based microplastics on anaerobic digestion: A review - Zezhou Shang; Rui Wang; Xiyi Zhang; Yongle Tu; Chenjing Sheng; Huan Yuan; Lei Wen; Yulu Li; Jing Zhang; Xiaojiao Wang; Gaihe Yang; Yongzhong Feng; et al. (Science of The Total Environment, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

Experimental study on the movement law of overlying rock non-pillar coal overhead mining - Yong Li; Jing Zheng; Feng-nian Wang; Xin-gen Ma; Rui-xue Zhang; Ying-ying Sun; Jian-bin Yin; Zhi-gang Tao (Journal of Mountain Science, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Short-term effect of apparent temperature on daily hospitalizations for osteoporotic fractures in Beijing, China: A retrospective observational study - Shuai Lu; Xuejiao Liu; Yanlin Niu; Feng Li; Maoqi Gong; Yejun Zha; Qingchen Chao; Bo Lu; Baichao Zhang; Ning Li; Jia Chen; Qiyong Liu; et al. (Science of The Total Environment, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

Diversity and distribution variation of urban spontaneous vegetation with distinct frequencies along river corridors in a fast-growing city - Xiaopeng Li; Sining Zhang; Rui Huang; Li Feng; Sihui Xu; Baichuan Liu (Journal of Environmental Management, 2023)

Prediction of vitrinite reflectance of shale oil reservoirs using nuclear magnetic resonance and conventional log data - Cheng Feng; Ziyan Feng; Rui Mao; Guanglei Li; Yuntao Zhong; Kegang Ling (Fuel, 2023)

Cognitive outcomes caused by low-level lead, cadmium, and mercury mixture exposure at distinct phases of brain development - Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Yanhui Zhu; Guihua Du; Jie Xie; Fankun Zhou; Chang Feng; Guangqin Fan (Food and Chemical Toxicology, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Forward osmosis membrane doped with water-based zirconium fumarate MOFs to enhance dye pollutant removal and membrane antifouling performance - Miaolu He; Leihao Feng; Qi Cui; Yushuang Li; Jiaqi Wang; Jiani Zhu; Lei Wang; Xudong Wang; Rui Miao (Environmental Science and Pollution Research, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

Endoplasmic reticulum stress regulates autophagic response that is involved in Saikosaponin a-induced liver cell damage - Ye-Feng Wang; Rui-Xia Ma; Bin Zou; Jia Li; Yao Yao; Juan Li (Toxicology in Vitro, 2023)

Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Inhibition of human sulfotransferases (SULTs) by per- and polyfluoroalkyl substances (PFASs) and structure-activity relationship - Yong-Zhe Liu; Kai Yang; Wei Zhang; Qian zhang; Tong-Feng Liu; Tong Xu; Yang Li; Rui-Xue Ran; Kun Yang; Yun-Feng Cao; Zhong-Ze Fang (Food and Chemical Toxicology, 2023)

New insights into photochemical initial concentrations of VOCs and their source implications - Bowei Li; Shaocai Yu; Min Shao; Xinhe Li; Steven Sai Hang Ho; Xiaoyi Hu; Hongli Wang; Rui Feng; Xuekun Fang (Atmospheric Environment, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Molecular Hydrogen: an Emerging Therapeutic Medical Gas for Brain Disorders - Chongyun Wu; Peibin Zou; Shu Feng; Ling Zhu; Fanghui Li; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Determination and prediction of digestible energy, metabolizable energy, and standardized ileal digestibility of amino acids in barley for growing pig - Rui Li; Mingzhou Tian; Ganyi Feng; Gaifeng Hou; Xianji Jiang; Gang Yang; Qiang Xiang; Xiaojie Liu; Cimi Long; Ruilin Huang; Yulong Yin (Animal Feed Science and Technology, 2023)

Tunable nanochannel resistive pulse sensing device using a novel multi-module self-assembly - Wenwei Pan; Rui You; Shuaihua Zhang; Ye Chang; Feng Zhou; Quanning Li; Xuejiao Chen; Xuexin Duan; Ziyu Han (Analytica Chimica Acta, 2023)

Pulsed turbidite and methane seep records in the north western South China Sea since the last glacial maximum - Jingrui Li; Xiaoming Miao; Xiuli Feng; Rui Jiang; Mengwei Zhao; Xiaopeng Dan; Qianwen Xiao; Jiangong Wei (Frontiers in Marine Science, 2023)
The small-scale event layers in the continental margin contain abundant dynamic environment information, and pose a challenge to the interpretation of continuous sedimentary records, giving geological significance to their accurate identify and possible genesis. Here, pulsed turbidite layers since the last glacial maximum (LGM) in a gravity core in the northwestern South China Sea (SCS) was analyzed to investigate the precisely identification, possible causes and the role of marine environmental change during the late Quaternary in formation of these small-scale event layers in the SCS. Eight potential pulsed turbidite layers, according to the petrographic characteristics, grain size parameters and element geochemistry, were identified. Meanwhile, indicators including total sulfur (TS)/total organic carbon (TOC) ratio, CaCO 3 content, and chromium-reducible sulfur (CRS) revealed these horizons were mostly related to methane seep events. Constrained by foraminifera shells AMS 14 C results, these events were determined to have occurred from the LGM to early Holocene, Similar records in the northern and southern slopes suggests the universal occurrence of these small-scale layers in the SCS. The comprehensive analysis showed that the development of these event layers over the past 25 ka can be divided into three stages, 25-15.5 ka, 15.5-7 ka and 7 ka to present. Late Quaternary Ocean environment changes, especially sea level and bottom water temperature, controlled the occurrence of regional small-scale event layers in the SCS. The regional scale mechanism is that the pressure and temperature change affect the stability of hydrate and the methane seepage, and thus the strata stability. Corresponding to the lowest, the rapid increase and the highest levels of the sea level and bottom water temperature, the temporal evolution pattern of small-scale event layers in the SCS showed a highest, decreased and lowest frequency, respectively. The linkage between the late Quaternary marine environmental change and turbidite deposition through gas activities in this study can act as a useful reference for further understanding the continental margin sedimentary process.

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

Creation of intermuscular bone-free mutants in amphitriploid gibel carp by editing two duplicated runx2b homeologs - Rui-Hai Gan; Zhi Li; Zhong-Wei Wang; Xi-Yin Li; Yang Wang; Xiao-Juan Zhang; Jin-Feng Tong; Yue Wu; Ling-Yun Xia; Ze-Xia Gao; Li Zhou; Jian-Fang Gui (Aquaculture, 2023)

Characteristics and source apportionment of some halocarbons in Hangzhou, eastern China during 2021 - Xinhe Li; Bowei Li; Yang Yang; Liting Hu; Di Chen; Xiaoyi Hu; Rui Feng; Xuekun Fang (Science of The Total Environment, 2023)

Infant food production environments: A potential reservoir for vancomycin-resistant enterococci non-nosocomial infections - Zining Wang; Sihao Liao; Guanwen Huang; Mengyao Feng; Rui Yin; Lin Teng; Chenghao Jia; Yicheng Yao; Min Yue; Yan Li (International Journal of Food Microbiology, 2023)

Pregnancy and lactation mixed exposure to lead, cadmium, and mercury alters maternal-offspring single heavy metal load: A factorial design - Guihua Du; Fankun Zhou; Lu Ouyang; Kai Wang; Shaoqi Rao; Rui Su; Yanhui Zhu; Kechu Guo; Jinmei Xiao; Jie Xie; Qi Li; Chang Feng; et al. (International Journal of Hygiene and Environmental Health, 2023)

Effects of Alpine Grassland Degradation on Soil Microbial Communities in Qilian Mountains of China - Chunming Li; Derong Zhang; Gengchun Xu; Rui Yan; Yang Huang; Liuqing Feng; Jin Yi; Xiangyu Xue; Huixia Liu (Journal of Soil Science and Plant Nutrition, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Isolation of atrazine nanobodies enhanced by depletion of anti-carrier protein phages and performance comparison between the nanobody and monoclonal antibody derived from the same immunogen - Qingqing He; Mian Wang; Yajie Zhao; Guiyu Tan; Man Zhang; Rui Feng; Yujie Chen; Baomin Wang; Qing X. Li (Analytica Chimica Acta, 2023)

Selenium alleviates endoplasmic reticulum calcium depletion-induced endoplasmic reticulum stress and apoptosis in chicken myocardium after mercuric chloride exposure - Pei-Chao Gao; An-Qi Wang; Xue-Wei Chen; Han Cui; Yue Li; Rui-Feng Fan (Environmental Science and Pollution Research, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

Microbial-induced calcium carbonate precipitation: Influencing factors, nucleation pathways, and application in waste water remediation - Yu Liu; Amjad Ali; Jun-Feng Su; Kai Li; Rui-Zhu Hu; Zhao Wang (Science of The Total Environment, 2023)

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Microwave-assisted co-precipitation preparation of CuFe2O4 photo-Fenton degradation tetracycline: Characterization, efficacy, stability in complex water quality and mechanism - Xiyu Sun; Guangzhi Wang; Likun Huang; Huanzhang Feng; Simin Zhou; Rui Zhao; Dongdong Wang; Zhe Li (Journal of Environmental Chemical Engineering, 2023)

Pioneering observation of atmospheric volatile organic compounds in Hangzhou in eastern China and implications for upcoming 2022 Asian Games - Bowei Li; Steven Sai Hang Ho; Xinhe Li; Liya Guo; Rui Feng; Xuekun Fang (Journal of Environmental Sciences, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The protective effect of Eleutheroside E against the mechanical barrier dysfunction triggered by lipopolysaccharide in IPEC-J2 cells - Huijuan Li; Rui Han; Feng Yong; Yueli Fan; Bao Zhao; Xiaocai Hu; Tianrui Zhang; Dongsheng Che (Research in Veterinary Science, 2023)

Mechanism of excavation-induced cracking of the protective layer of a rock bench in a large underground powerhouse under high tectonic stress - Yuelin Xia; Xia-Ting Feng; Chengxiang Yang; Shaojun Li; Dingping Xu; Quan Jiang; Rui Kong; Yonghong Li; Zhiguo Li (Engineering Geology, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Temperature-gradient-induced enhanced fog collection on polymer brush surfaces - Zheng-Hong Liang; Rui Feng; Jia-Min Wu; Dong Li; Fang Wang; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Water-soluble brown carbon in PM2.5 at two typical sites in Guanzhong Basin: Optical properties, sources, and implications - Xiaofei Li; Feng Yu; Yiying Song; Chao Zhang; Fangping Yan; Zhaofu Hu; Yali Lei; Lekhendra Tripathee; Rui Zhang; Jingning Guo; Yuqin Wang; Qingcai Chen; et al. (Atmospheric Research, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Effects of Spartina alterniflora Invasion and Mangrove Restoration on Soil Microbial Functional Diversity - Yongni He; Genmei Lin; Xinyi Gao; Yiting Cao; Naxu Hu; Rui Li; Jianxiang Feng (Journal of Soil Science and Plant Nutrition, 2022)

Baicalin-berberine complex nanocrystals orally promote the co-absorption of two components - Ziwei Li; Yiting Liu; Jilin Wang; Xiaojiao Feng; Ebuka-Olisaemeka Nwafor; Ying Zhang; Rui Liu; Wenli Dang; Qingqing Zhang; Changxiang Yu; Jiaxin Pi; Zhidong Liu (Drug Delivery and Translational Research, 2022)

Effects of STAT3 Inhibitor BP-1-102 on The Proliferation, Invasiveness, Apoptosis and Neurosphere Formation of Glioma Cells in Vitro - Cheng-Chen Zhang; Ting Wu; Li Guan; Yu-Jue Wang; Rui-Qin Yao; Dian-Shuai Gao; Feng Li (Cell Biochemistry and Biophysics, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Three new compounds from the leaves of Castanopsis tibetana Hance - Ya-Feng Wang; Rui-Jie He; Dian-Peng Li; Yong-Lin Huang (Natural Product Research, 2022)

Triphenylpyrazoline ketone chlorophenols as potential candidate compounds against Parkinson’s disease: design, synthesis, and biological evaluation - Ning Ning Cheng; Le Hua Zhang; Rui Ge; Xiu E. Feng; Qing Shan Li (Medicinal Chemistry Research, 2022)

Orbit determination, clock estimation and performance evaluation of BDS-3 PPP-B2b service - Chengpan Tang; Xiaogong Hu; Jinping Chen; Li Liu; Shanshi Zhou; Rui Guo; Xiaojie Li; Feng He; Jinhuo Liu; Jianhua Yang (Journal of Geodesy, 2022)

Association between ambient air pollution exposure during pregnancy and gestational diabetes mellitus: a meta-analysis of cohort studies - Xinyu Zhou; Changlian Li; Han Cheng; Junyi Xie; Feng Li; Lishan Wang; Rui Ding (Environmental Science and Pollution Research, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Spatial-temporal distribution and tectonic setting of Mesozoic W-mineralized granitoids in the Xing-Meng Orogenic Belt, NE China - Wei Xie; Qing-Dong Zeng; Rui-Liang Wang; Jin-Jian Wu; Zhe-Ming Zhang; Feng-Chun Li; Zhuang Zhang (International Geology Review, 2022)

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Failure mechanisms and risk mitigation of check dams on the Chinese Loess Plateau: A case study at the Gutun Gully - Rui-jun Jiang; Mao-sheng Zhang; Li Feng; Ping-ping Sun (Journal of Mountain Science, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

The Antioxidant Role of Selenium via GPx1 and GPx4 in LPS-Induced Oxidative Stress in Bovine Endometrial Cells - Samson O. Adeniran; Peng Zheng; Rui Feng; Elikanah O. Adegoke; Fushuo Huang; Mingjun Ma; Ziming Wang; Olamigoke O. Ifarajimi; Xiaoyu Li; Guixue Zhang (Biological Trace Element Research, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Long-term observations of the chemical composition, fluxes and sources of atmospheric wet deposition at an urban site in Xi’an, Northwest China - Rui-feng Li; Xi-ying Dong; Cong Xie; Liang-ju Zhao (Environmental Monitoring and Assessment, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Existing form and distribution of fluorine and phosphorus in phosphate rock acid-insoluble residue - Rui Li; Weilong He; Jiangfei Duan; Shengxia Feng; Ziyu Zhu; Yu Zhang (Environmental Science and Pollution Research, 2022)

Variations in bacterial and archaeal community structure and diversity along the soil profiles of a peatland in Southwest China - Wei Li; Mingmo Luo; Rui Shi; Defeng Feng; Zhenan Yang; Huai Chen; Bin Hu (Environmental Science and Pollution Research, 2022)

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Microbial ecology of sulfur cycling near the sulfate–methane transition of deep‐sea cold seep sediments - Wen‐Li Li; Xiyang Dong; Rui Lu; Ying‐Li Zhou; Peng‐Fei Zheng; Dong Feng; Yong Wang (Environmental Microbiology, 2021)
Summary Microbial sulfate reduction is largely associated with anaerobic methane oxidation and alkane degradation in sulfate–methane transition zone (SMTZ) of deep‐sea cold seeps. How the sulfur cycling is mediated by microbes near SMTZ has not been fully understood. In this study, we detected a shallow SMTZ in three of eight sediment cores sampled from two cold seep areas in the South China Sea. One hundred ten genomes representing sulfur‐oxidizing bacteria (SOB) and sulfur‐reducing bacteria (SRB) strains were identified from three SMTZ‐bearing cores. In the layers above SMTZ, SOB were mostly constituted by Campylobacterota, Gammaproteobacteria and Alphaproteobacteria that probably depended on nitrogen oxides and/or oxygen for oxidation of sulfide and thiosulfate in near‐surface sediment layers. In the layers below the SMTZ, the deltaproteobacterial SRB genomes and metatranscriptomes revealed CO 2 fixation by Wood–Ljungdahl pathway, sulfate reduction and nitrogen fixation for syntrophic or fermentative lifestyle. A total of 68% of the metagenome assembled genomes were not adjacent to known species in a phylogenomic tree, indicating a high diversity of bacteria involved in sulfur cycling. With the large number of genomes for SOB and SRB, our study uncovers the microbial populations that potentially mediate sulfur metabolism and associated carbon and nitrogen cycles, which sheds light on complex biogeochemical processes in deep‐sea environments.

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

A massive ancient river-damming landslide triggered by buckling failure in the upper Jinsha River, SE Tibetan Plateau - Yanyan Li; Xuyang Feng; Aijun Yao; Shan Lin; Rui Wang; Mingzhu Guo (Bulletin of Engineering Geology and the Environment, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Fast and accurate detection of kiwifruit in orchard using improved YOLOv3-tiny model - Longsheng Fu; Yali Feng; Jingzhu Wu; Zhihao Liu; Fangfang Gao; Yaqoob Majeed; Ahmad Al-Mallahi; Qin Zhang; Rui Li; Yongjie Cui (Precision Agriculture, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

Dyad sex composition effect on inter-brain synchronization in face-to-face cooperation - Yuhua Li; Rui Chen; Ofir Turel; Tingyong Feng; Chao-Zhe Zhu; Qinghua He (Brain Imaging and Behavior, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Double Weighted Sparse Nonnegative Tensor Factorization for Hyperspectral Unmixing - Heng-Chao Li; Shuang Liu; Xin-Ru Feng; Rui Wang; Yong-Jian Sun (International Journal of Remote Sensing, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Sphingobacterium endophyticum sp. nov., a novel endophyte isolated from halophyte - Yang-Yang Liu; Fang Liu; Yu-Qian Li; Rui-Feng Lei; Qin Ma; Manik Prabhu Narsing Rao; Dilireba Abudourousuli; Zulihumaer Rouzi; Muyesaier Aosiman; Deng-Di An; Wen-Jun Li (Archives of Microbiology, 2020)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

MELK Accelerates the Progression of Colorectal Cancer via Activating the FAK/Src Pathway - Guangming Liu; Wei Zhan; Wei Guo; Feng Hu; Junjie Qin; Rui Li; Xin Liao (Biochemical Genetics, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Cloning and expression of Allophycocyanin gene from Gracilariopsis lemaneiformis and studying the binding sites of phycocyanobilin on its α and β subunits - Yalin Guo; Xiaonan Zang; Xuexue Cao; Feng Zhang; Deguang Sun; Menghui Shang; Rui Li; Zhaxi Yangzong; Xuehong Wei; Xuecheng Zhang (Journal of Applied Phycology, 2020)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Moderate parasitoidism on pollinators contributes to population oscillations and increases species diversity in the fig-fig wasp community - Lin Wang; Li-Yuan Yang; Feng Zhang; Rui-Wu Wang (Theoretical Ecology, 2020)

Rapid and efficient removal of naproxen from water by CuFe2O4 with peroxymonosulfate - Rui Bai; Yong Xiao; Weifu Yan; Siqi Wang; Rui Ding; Fan Yang; Junpeng Li; Xiaoquan Lu; Feng Zhao (Environmental Science and Pollution Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

First report of broad bean wilt virus 2 infection in eggplant in China - Peng-Huan Rui; Lei Jiang; Shuai Li; Xi-Zi Jiang; Qing-Qing Zhao; Ji Ying Feng; Tong Jiang (Journal of Plant Pathology, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Quantitative proteomic analysis reveals that the Rap1/MAPK/ERK pathway is inhibited through selenomethionine strengthening antioxidant activity - Zhe Liu; Feng Zhang; Lina Cui; Jihong Wang; Ping Lu; Rui Zhao; Hua Zhang; Jianfa Wang; Chunqiu Li; Rui Wu (BioMetals, 2020)

PDGFRβ-targeted TRAIL specifically induces apoptosis of activated hepatic stellate cells and ameliorates liver fibrosis - Rui Li; Zhao Li; Yanru Feng; Hao Yang; Qiuxiao Shi; Ze Tao; Jingqiu Cheng; Xiaofeng Lu (Apoptosis, 2020)

Systematic analysis of lncRNA expression profiles and atherosclerosis-associated lncRNA-mRNA network revealing functional lncRNAs in carotid atherosclerotic rabbit models - Yingnan Wu; Feng Zhang; Xiaoying Li; Wenying Hou; Shuang Zhang; Yanan Feng; Rui Lu; Yu Ding; Litao Sun (Functional & Integrative Genomics, 2020)

Selenium Mitigates Cadmium-Induced Adverse Effects on Trace Elements and Amino Acids Profiles in Chicken Pectoral Muscles - Kui-Chao Qu; Hui-Qin Li; Kou-Kou Tang; Zhen-Yong Wang; Rui-Feng Fan (Biological Trace Element Research, 2020)

CD271 promotes STZ-induced diabetic wound healing and regulates epidermal stem cell survival in the presence of the pTrkA receptor - Min Zhang; Rui Zhang; Xiaohong Li; Yongqian Cao; Kaifeng Huang; Jun Ding; Mengyao Liu; Zhang Feng; Siyuan Yin; Jiaxu Ma; Huayu Zhang; Yibing Wang (Cell and Tissue Research, 2020)

A transcriptome analysis uncovers Panax notoginseng resistance to Fusarium solani induced by methyl jasmonate - Diqiu Liu; Qin Zhao; Xiuming Cui; Rui Chen; Xin Li; Bingling Qiu; Feng Ge (Genes & Genomics, 2019)

Yeast cell walls stimulate viability, respiratory burst, and phagocytosis in channel catfish (Ictalurus punctatus) head-kidney macrophages - Jianjun Zhou; Zhen Gao; Wenbiao Wang; Feng Huang; Junpeng Hu; Aqiong Gong; Rui Wang; Wumin Yang; Jie Li; Xianqin Hu; Xuedong Wang (Aquaculture International, 2019)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

Soil water content and pH drive archaeal distribution patterns in sediment and soils of water-level-fluctuating zones in the East Dongting Lake wetland, China - Wei Li; Defeng Feng; Gang Yang; Zhengmiao Deng; Junpeng Rui; Huai Chen (Environmental Science and Pollution Research, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

ATP induces caspase-3/gasdermin E-mediated pyroptosis in NLRP3 pathway-blocked murine macrophages - Chen-Ying Zeng; Chen-Guang Li; Jun-Xiang Shu; Li-Hui Xu; Dong-Yun Ouyang; Feng-Yi Mai; Qiong-Zhen Zeng; Cheng-Cheng Zhang; Rui-Man Li; Xian-Hui He (Apoptosis, 2019)

Fluorophenols bearing nitrogenated heterocycle moieties, a class of novel Keap1-Nrf2 protein-protein interaction inhibitors: synthesis, antioxidant stress screening and molecular docking - Xiu E Feng; De Peng Kong; Shu Rong Ban; Rui Ge; Qing Shan Li (Medicinal Chemistry Research, 2019)

Selenium alleviates cadmium-induced inflammation and meat quality degradation via antioxidant and anti-inflammation in chicken breast muscles - Kou-Kou Tang; Hui-Qin Li; Kui-Chao Qu; Rui-Feng Fan (Environmental Science and Pollution Research, 2019)

Selenium-Yeast Alleviated Inflammatory Damage Caused by Lead via Inhibiting Ras/ERK Pathway and Inflammatory Factors in Chicken Skeletal Muscles - Zhe Liu; Feng Zhang; Ping Lu; Rui Zhao; Hua Zhang; Baifen Song; Liyang Li; Zhijun Wu; Rui Wu (Biological Trace Element Research, 2019)

Gut microbiota in patients after surgical treatment for colorectal cancer - Ye Jin; Yang Liu; Lei Zhao; Fuya Zhao; Jing Feng; Shengda Li; Huinan Chen; Jiayu Sun; Biqiang Zhu; Rui Geng; Yunwei Wei (Environmental Microbiology, 2019)
Summary Colorectal cancer (CRC) is a common disease worldwide that is strongly associated with the gut microbiota. However, little is known regarding the gut microbiota after surgical treatment. 16S rRNA gene sequencing was used to evaluate differences in gut microbiota among colorectal adenoma patients, CRC patients, CRC postoperative patients and healthy controls by comparing gut microbiota diversity, overall composition and taxonomic signature abundance. The gut microbiota of CRC patients, adenoma patients and healthy controls developed in accordance with the adenoma‐carcinoma sequence, with impressive shifts in the gut microbiota before or during the development of CRC. The gut microbiota of postoperative patients and CRC patients differed significantly. Subdividing CRC postoperative patients according to the presence or absence of newly developed adenoma which based on the colonoscopy findings revealed that the gut microbiota of newly developed adenoma patients differed significantly from that of clean intestine patients and was more similar to the gut microbiota of carcinoma patients than to the gut microbiota of healthy controls. The alterations of the gut microbiota between the two groups of postoperative patients corresponded to CRC prognosis. More importantly, we used the different gut microbiota as biomarkers to distinguish postoperative patients with or without newly developed adenoma, achieving an AUC value of 0.72. These insights on the changes in the gut microbiota of CRC patients after surgical treatment may allow the use of the microbiota as non‐invasive biomarkers for the diagnosis of newly developed adenomas and to help prevent cancer recurrence in postoperative patients.

Inhibition of YAP with siRNA prevents cartilage degradation and ameliorates osteoarthritis development - Yong Gong; Song-Jian Li; Rui Liu; Jian-Feng Zhan; Chao Tan; Yi-Fei Fang; Yan Chen; Bo Yu (Journal of Molecular Medicine, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Functional brain abnormalities in major depressive disorder using the Hilbert-Huang transform - Haibin Yu; Feng Li; Tong Wu; Rui Li; Li Yao; Chuanyue Wang; Xia Wu (Brain Imaging and Behavior, 2018)

Analysis of Sedimentary Components in Post-haze Concentrated Sugarcane Juice - Rui-Jing Qu; Kai Li; Fang-Xue Hang; Wen Li; Cai-Feng Xie (Sugar Tech, 2018)

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

Pyrite textures and compositions from the Zhuangzi Au deposit, southeastern North China Craton: implication for ore-forming processes - Xing-Hui Li; Hong-Rui Fan; Kui-Feng Yang; Pete Hollings; Xuan Liu; Fang-Fang Hu; Ya-Chun Cai (Contributions to Mineralogy and Petrology, 2018)

The Involvement of Cytochrome c Oxidase in Mitochondrial Fusion in Primary Cultures of Neonatal Rat Cardiomyocytes - Wen Yin; Rui Li; Xiaorong Feng; Y. James Kang (Cardiovascular Toxicology, 2018)

Time is nothing: emotional consistency of autobiographical memory and its neural basis - Rui Xu; Juan Yang; Chunliang Feng; Haiyan Wu; Ruiwang Huang; Qiuli Yang; Zhihao Li; Pengfei Xu; Ruolei Gu; Yue-jia Luo (Brain Imaging and Behavior, 2018)

Land-use change alters patterns of soil biodiversity in arid lands of northwestern China - Feng-Rui Li; Ji-Liang Liu; Wei Ren; Lu-Lu Liu (Plant and Soil, 2018)

Alleviation of Arsenic-Induced Pulmonary Oxidative Damage by GSPE as Shown during In vivo and In vitro Experiments - Meng Wei; Fangming Guo; Dongsheng Rui; Haixia Wang; Gangling Feng; Shugang Li; Guanling Song (Biological Trace Element Research, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

U–Pb zircon, geochemical and Sr–Nd–Hf isotopic constraints on age and origin of the intrusions from Wunugetushan porphyry deposit, Northeast China: implication for Triassic–Jurassic Cu–Mo mineralization in Mongolia–Erguna metallogenic belt - Kui-Feng Mi; Zhen-Jiang Liu; Rui-Bin Liu; Chun-Feng Li; Jian-Ping Wang; Run-Min Peng (International Geology Review, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

The Arc Gene Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Rui Bi; Li-Li Kong; Min Xu; Guo-Dong Li; Deng-Feng Zhang; Tao Li; Yiru Fang; Chen Zhang; Buchang Zhang; Yong-Gang Yao (Molecular Neurobiology, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

The higher grain production, the more social deprivation? A case study of Henan province in traditional agricultural areas of China - Jun-bo Gao; Wei-feng Qiao; Yan-sui Liu; Yu-rui Li; Wei Tu; Yong-xian Zhang (Journal of Mountain Science, 2018)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

The use of toluidine blue staining combined with paraffin sectioning and the optimization of freeze-thaw counting methods for analysing root-knot nematodes in tomato - Xiaoman Li; Wenchao Zhao; Xiaoxuan Zhou; Jiaping Feng; Yingjian Gao; Xuehui Yao; Yang Liu; Jie Liu; Rui Yang; Fukuan Zhao; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2017)

ABA pretreatment enhances the chilling tolerance of a chilling-sensitive rice cultivar - Xiang Hongtao; Wang Tongtong; Zheng Dianfeng; Wang Lizhi; Feng Yanjiang; Luo Yu; Li Rui; Li Zhongjie; Meng Ying; Li Wan; Wang Lianmin; Yang Chunjie (Brazilian Journal of Botany, 2017)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Behavioral responses of the egg parasitoid Trissolcus japonicus to volatiles from adults of its stink bug host, Halyomorpha halys - Yong-Zhi Zhong; Jin-Ping Zhang; Li-Li Ren; Rui Tang; Hai-Xia Zhan; Guo-Hua Chen; Feng Zhang (Journal of Pest Science, 2017)

Spatiotemporal Variability of Contaminants in Lake Water and Their Risks to Human Health: A Case Study of the Shahu Lake Tourist Area, Northwest China - Peiyue Li; Wei Feng; Chenyang Xue; Rui Tian; Siting Wang (Exposure and Health, 2017)

Oxidative Damage Induced by Arsenic in Mice or Rats: A Systematic Review and Meta-Analysis - Mengchuan Xu; Dongsheng Rui; Yizhong Yan; Shangzhi Xu; Qiang Niu; Gangling Feng; Yan Wang; Shugang Li; Mingxia Jing (Biological Trace Element Research, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

Costimulation of soil glycosidase activity and soil respiration by nitrogen addition - Ji Chen; Yiqi Luo; Jianwei Li; Xuhui Zhou; Junji Cao; Rui‐Wu Wang; Yunqiang Wang; Shelby Shelton; Zhao Jin; Laura M. Walker; Zhaozhong Feng; Shuli Niu; et al. (Global Change Biology, 2017)
Unprecedented levels of nitrogen (N) have been deposited in ecosystems over the past century, which is expected to have cascading effects on microbially mediated soil respiration ( SR ). Extracellular enzymes play critical roles on the degradation of soil organic matter, and measurements of their activities are potentially useful indicators of SR . The links between soil extracellular enzymatic activities ( EEA s) and SR under N addition, however, have not been established. We therefore conducted a meta‐analysis from 62 publications to synthesize the responses of soil EEA s and SR to elevated N. Nitrogen addition significantly increased glycosidase activity ( GA ) by 13.0%, α ‐1,4‐glucosidase ( AG ) by 19.6%, β ‐1,4‐glucosidase ( BG ) by 11.1%, β ‐1,4‐xylosidase ( BX ) by 21.9% and β ‐D‐cellobiosidase ( CBH ) by 12.6%. Increases in GA were more evident for long duration, high rate, organic and mixed N addition (combination of organic and inorganic N addition), as well as for studies from farmland. The response ratios ( RR s) of GA were positively correlated with the SR ‐ RR s, even when evaluated individually for AG , BG , BX and CBH . This positive correlation between GA ‐ RR and SR ‐ RR was maintained for most types of vegetation and soil as well as for different methods of N addition. Our results provide the first evidence that GA is linked to SR under N addition over a range of ecosystems and highlight the need for further studies on the response of other soil EEA s to various global change factors and their implications for ecosystem functions.

Nurr1 promotes intestinal regeneration after ischemia/reperfusion injury by inhibiting the expression of p21 (Waf1/Cip1) - Guo Zu; Jihong Yao; Anlong Ji; Shili Ning; Fuwen Luo; Zhenlu Li; Dongcheng Feng; Yiqi Rui; Yang Li; Guangzhi Wang; Xiaofeng Tian (Journal of Molecular Medicine, 2017)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

The ROS derived mitochondrial respirstion not from NADPH oxidase plays key role in Celastrol against angiotensin II-mediated HepG2 cell proliferation - Xin Liu; Rui-wei Gao; Miao Li; Chun-feng Si; Yong-peng He; Min Wang; Ying Yang; Qing-yin Zheng; Chao-yun Wang (Apoptosis, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Culture of shoot tips from adventitious shoots can eradicate Apple stem pitting virus but fails in Apple stem grooving virus - Min-Rui Wang; Bai-Quan Li; Chao-Hong Feng; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Effects of organic matter content and composition on ammonium adsorption in lake sediments - Li Zhang; Shengrui Wang; Lixin Jiao; Yanping Li; Jiachun Yang; Rui Zhang; Shuang Feng; Juan Wang (Environmental Science and Pollution Research, 2016)

Sequence Characteristics and Phylogenetic Implications of the nrDNA Internal Transcribed Spacers (ITS) in Protospecies and Landraces of Sugarcane (Saccharum officinarum L.) - Cui-Feng Yang; Li-Tao Yang; Yang-Rui Li; Ge-Min Zhang; Chun-Ya Zhang; Wei-Zan Wang (Sugar Tech, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

p55γ functional mimetic peptide N24 blocks vascular proliferative disorders - Jiaojiao Guo; Ning Xie; Geng Li; Yan Zhang; Fengxiang Lv; Sile Guo; Yuanqing Feng; Chun-Mei Cao; Rui-Ping Xiao (Journal of Molecular Medicine, 2015)

Mutations in human IFT140 cause non-syndromic retinal degeneration - Mingchu Xu; Lizhu Yang; Feng Wang; Huajin Li; Xia Wang; Weichen Wang; Zhongqi Ge; Keqing Wang; Li Zhao; Hui Li; Yumei Li; Ruifang Sui; et al. (Human Genetics, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Numerical Simulation of Coronary Artery Stenosis Before and After Stenting - Gang Li; Rui Hu; Feng Gao (Journal of Medical and Biological Engineering, 2015)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

The concentration of selenium matters: a field study on mercury accumulation in rice by selenite treatment in qingzhen, Guizhou, China - Yu-Feng Li; Jiating Zhao; Yunyun Li; Hanjun Li; Junfang Zhang; Bai Li; Yuxi Gao; Chunying Chen; Manyi Luo; Rui Huang; Jun Li (Plant and Soil, 2015)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

A Controlled Study of Alprostadil Liposomal Preparation in the Treatment of Blue Toe Syndrome - Hai-lin Xi; Rui Li; Zhi-long Tian; Su Feng; Gao-Lei Jia (Cell Biochemistry and Biophysics, 2015)

Heterologous expression and characterization of a novel halotolerant, thermostable, and alkali-stable GH6 endoglucanase from Thermobifida halotolerans - Yi-Rui Yin; Feng Zhang; Qing-Wen Hu; Wen-Dong Xian; Wael N. Hozzein; En-Min Zhou; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Biotechnology Letters, 2015)

Production and Characteristics of High Quality Vinegar from Sugarcane Juice - Gan-Lin Chen; Feng-Jin Zheng; Jian Sun; Zhi-Chun Li; Bo Lin; Yang-Rui Li (Sugar Tech, 2015)

Effect of Drought Stress on Anatomical Structure and Chloroplast Ultrastructure in Leaves of Sugarcane - Feng-Juan Zhang; Kun-Kun Zhang; Cheng-Zhong Du; Jian Li; Yong-Xiu Xing; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Recent climate warming of central China reflected by temperature-sensitive tree growth in the eastern Qinling Mountains and its linkages to the Pacific and Atlantic oceans - Feng Chen; Rui-bo Zhang; Hui-qin Wang; Li Qin (Journal of Mountain Science, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Ground-dwelling arthropod community response to native grassland conversion in a temperate desert of northwestern China - Qi Feng; Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Li-Juan Chen (Journal of Insect Conservation, 2015)

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

Rock Burst Intensity Classification Based on the Radiated Energy with Damage Intensity at Jinping II Hydropower Station, China - Bing-Rui Chen; Xia-Ting Feng; Qing-Peng Li; Ru-Zhou Luo; Shaojun Li (Rock Mechanics and Rock Engineering, 2015)

H2O2 Induces Myocardial Hypertrophy in H9c2 Cells: A Potential Role of Ube3a - Rui Song; Jie Zhang; Lijuan Zhang; Guanghua Wang; Da Wo; Jian Feng; Xucheng Li; Jue Li (Cardiovascular Toxicology, 2015)

An 18-element GEO broadcast ephemeris based on non-singular elements - Lan Du; Zhongkai Zhang; Jin Zhang; Li Liu; Rui Guo; Feng He (GPS Solutions, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Investigation on Etiology of Hepatic Venous Obstruction Budd-Chiari Syndrome - Zhi-Long Tian; Gao-Lei Jia; Hai-Lin Xi; Su Feng; Xiao-Kai Wang; Rui Li (Cell Biochemistry and Biophysics, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Microseismic monitoring of columnar jointed basalt fracture activity: a trial at the Baihetan Hydropower Station, China - Bing-Rui Chen; Qing-Peng Li; Xia-Ting Feng; Ya-Xun Xiao; Guang-Liang Feng; Lian-Xing Hu (Journal of Seismology, 2014)

DNA Methylation: Roles in Rheumatoid Arthritis - Feng-Lai Yuan; Xia Li; Rui-Sheng Xu; Dong-Lin Jiang; Xiao-Gang Zhou (Cell Biochemistry and Biophysics, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Shoot regeneration and cryopreservation of shoot tips of apple (Malus) by encapsulation–dehydration - Bai-Quan Li; Chao-Hong Feng; Ling-Yun Hu; Min-Rui Wang; Long Chen; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

An automatic seismic signal detection method based on fourth-order statistics and applications - Xi-Qiang Liu; Yin Cai; Rui Zhao; Yin-Gang Zhao; Bao-An Qu; Zhi-Jun Feng; Hong Li (Applied Geophysics, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China - Lei Dong; Hong Ming; Yi-Rui Yin; Yan-Yan Duan; En-Min Zhou; Guo-Xing Nie; Hui-Geng Feng; Lan Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Zhizhongheella caldifontis gen. nov., sp. nov., a novel member of the family Comamonadaceae - Lei Dong; Hong Ming; Lan Liu; En-Min Zhou; Yi-Rui Yin; Yan-Yan Duan; Guo-Xing Nie; Hui-Geng Feng; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Molecular dynamics-based self-organizing molecular field analysis on 3-amino-6-arylpyrazines as the ataxia telangiectasia mutated and Rad3 related (ATR) protein kinase inhibitors - Hao Luo; Jianyou Shi; Lufei Lu; Feng Wu; Meng Zhou; Xueyan Hou; Wenjuan Zhang; Zhengyu Ding; Rui Li (Medicinal Chemistry Research, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

Preparation and Characteristics of Sugarcane Low Alcoholic Drink by Submerged Alcoholic Fermentation - Gan-Lin Chen; Feng-Jin Zheng; Bo Lin; Tian-Shun Wang; Yang-Rui Li (Sugar Tech, 2013)

Elevated risk of opportunistic viral infection in patients with Crohn’s disease during biological therapies: a meta analysis of randomized controlled trials - Xiaobing Wang; Feng Zhou; Junzhang Zhao; Rui Zhou; Meifang Huang; Jin Li; Wei Wang; Shufang Xu; Bing Xia (European Journal of Clinical Pharmacology, 2013)

Effects of the Conversion of Native Vegetation to Farmlands on Soil Microarthropod Biodiversity and Ecosystem Functioning in a Desert Oasis - Feng-Rui Li; Qi Feng; Ji-Liang Liu; Te-Sheng Sun; Wei Ren; Zhen-Huan Guan (Ecosystems, 2013)

Genome-wide Analysis of the Distribution of AP2/ERF Transcription Factors Reveals Duplication and Elucidates their Potential Function in Chinese Cabbage (Brassica rapa ssp. pekinensis) - Meng-Yao Li; Feng Wang; Qian Jiang; Rui Li; Jing Ma; Ai-Sheng Xiong (Plant Molecular Biology Reporter, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

The member of high temperature requirement family HtrA2 participates in neuronal apoptosis after intracerebral hemorrhage in adult rats - Huiqing Sun; Lei Li; Feng Zhou; Lin Zhu; Kaifu Ke; Xiang Tan; Wei Xu; Ying Rui; Heyi Zheng; Zhengming Zhou; Huiguang Yang (Journal of Molecular Histology, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Effect of total dissolved gas supersaturated water on early life of David’s schizothoracin (Schizothorax davidi) - Rui-feng Liang; Bo Li; Ke-feng Li; You-cai Tuo (Journal of Zhejiang University-SCIENCE B, 2013)

Complete disassociation of adult pancreas into viable single cells through cold trypsin-EDTA digestion - Dan Li; Shi-yun Peng; Zhen-wu Zhang; Rui-cheng Feng; Lu Li; Jie Liang; Sheng Tai; Chun-bo Teng (Journal of Zhejiang University-SCIENCE B, 2013)

High resource capture and use efficiency and prolonged growth season contribute to invasiveness of Eupatorium adenophorum - Wei-Bin Wang; Rui-Fang Wang; Yan-Bao Lei; Chao Liu; Li-Hong Han; Xiao-Dong Shi; Yu-Long Feng (Plant Ecology, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

The presence of Genogroup II Norovirus in Retail Shellfish from Seven Coastal Cities in China - Li-ping Ma; Feng Zhao; Lin Yao; Xin-guang Li; De-qing Zhou; Rui-ling Zhang (Food and Environmental Virology, 2013)

Shrubs and species identity effects on the distribution and diversity of ground-dwelling arthropods in a Gobi desert - Feng-Rui Li; Ji-Liang Liu; Chang-An Liu; Qi-Jun Liu; Rui-Xue Niu (Journal of Insect Conservation, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Screening level ecological risk assessment for synthetic musks in surface water of Lake Taihu, China - Guang-Hui Guo; Feng-Chang Wu; Hong-Ping He; Rui-Qing Zhang; Hui-Xian Li (Stochastic Environmental Research and Risk Assessment, 2013)

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Association of AFF1 rs340630 and AFF3 rs10865035 polymorphisms with systemic lupus erythematosus in a Chinese population - Han Cen; Rui-Xue Leng; Wei Wang; Mo Zhou; Chen-Chen Feng; Gui-Mei Chen; Rui Li; Hai-Feng Pan; Xiang-Pei Li; Dong-Qing Ye (Immunogenetics, 2012)

Impairment of liver regeneration by the histone deacetylase inhibitor valproic acid in mice - Qi Ke; Rui-na Yang; Feng Ye; Yu-jia Wang; Qiong Wu; Li Li; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2012)

Influences of shrub vegetation on distribution and diversity of a ground beetle community in a Gobi desert ecosystem - Ji-Liang Liu; Feng-Rui Li; Chang-An Liu; Qi-Jun Liu (Biodiversity and Conservation, 2012)

Mantle-derived noble gases in ore-forming fluids of the granite-related Yaogangxian tungsten deposit, Southeastern China - Rui-Zhong Hu; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Jian-Tang Peng; You-Qiang Qi; Li-Yan Wu; Wen-Feng Wei (Mineralium Deposita, 2012)

Screening for significant atherosclerotic renal artery stenosis with a regression model in patients undergoing transradial coronary angiography/intervention - Li-jin Pu; Ying Shen; Rui-yan Zhang; Qi Zhang; Lin Lu; Feng-hua Ding; Jian Hu; Zheng-kun Yang; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2012)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)

Distribution and linkage disequilibrium analysis of polymorphisms of MC4R, LEP, H-FABP genes in the different populations of pigs, associated with economic traits in DIV2 line - Zhe Chao; Feng Wang; Chang-Yan Deng; Li-Min Wei; Rui-Ping Sun; Hai-Long Liu; Quan-Wei Liu; Xin-Li Zheng (Molecular Biology Reports, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Dynamics of vegetation and soil carbon and nitrogen accumulation over 26 years under controlled grazing in a desert shrubland - Zhi-Yu Zhou; Feng-Rui Li; Shan-Ke Chen; Hong-Rong Zhang; Guangdi Li (Plant and Soil, 2011)

Targeting interleukin-21 in rheumatoid arthritis - Feng-Lai Yuan; Wei Hu; Wei-Guo Lu; Xia Li; Jian-Ping Li; Rui-Sheng Xu; Cheng-Wan Li; Fei-Hu Chen; Cheng Jin (Molecular Biology Reports, 2011)

Effect of host plants on development and reproduction of Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) - Rui-Ting Ju; Feng Wang; Fang-Hao Wan; Bo Li (Journal of Pest Science, 2011)

The emplacement mechanisms and growth styles of the Guposhan-Huashan batholith in western Nanling Range, South China - ZuoHai Feng; ChunZeng Wang; JinCheng Liang; JunZhao Li; YongGao Huang; JiaFei Liao; Rui Wang (Science China Earth Sciences, 2011)

TWEAK as a target for therapy in systemic lupus erythematosus - Rui-Xue Leng; Hai-Feng Pan; Wei-Zi Qin; Chao Wang; Li-Li Chen; Jin-Hui Tao; Dong-Qing Ye (Molecular Biology Reports, 2011)

The effect of the expression of angiotensin II on extracellular matrix metalloproteinase inducer (EMMPRIN) in macrophages is mediated via the AT1/COX-2/PGE2 pathway - Li-xia Yang; Jin-shan Ye; Rui-wei Guo; Hong Liu; Xian-mei Wang; Feng Qi; Chuanming Guo (Inflammation Research, 2010)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

The influence of ADAR1’s regulation on lymphocyte cell function during rejection - Lei Cai; Yan Li; Feng Liu; Wei Zhang; Binliang Huo; Wei Zheng; Rui Ding; Jiyuan Guo; Qingchuan Zhao; Kefeng Dou (Molecular Biology Reports, 2010)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Degradation of Polycyclic Aromatic Hydrocarbons by Crude Extracts from Spent Mushroom Substrate and its Possible Mechanisms - Xuanzhen Li; Xiangui Lin; Jing Zhang; Yucheng Wu; Rui Yin; Youzhi Feng; Yong Wang (Current Microbiology, 2010)

Dynamics of soil organic carbon and nitrogen associated with physically separated fractions in a grassland-cultivation sequence in the Qinghai-Tibetan plateau - Xiao Ming Shi; Xiao Gang Li; Rui Jun Long; Bhupinder Pal Singh; Zhuo Ting Li; Feng Min Li (Biology and Fertility of Soils, 2010)

Isolation and Analysis of Rice Rf1-Orthologus PPR Genes Co-segregating with Rf3 in Maize - Xiang-Bo Xu; Zhan-Xian Liu; Deng-Feng Zhang; Ying Liu; Wei-Bin Song; Jian-Sheng Li; Jing-Rui Dai (Plant Molecular Biology Reporter, 2009)

NMDA receptor antagonist MK-801 reduces neuronal damage and preserves learning and memory in a rat model of traumatic brain injury - Rui-Zhang Han; Jin-Jia Hu; Yuan-Chi Weng; Ding-Feng Li; Yi Huang (Neuroscience Bulletin, 2009)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

SSR and SCAR mapping of a multiple-allele male-sterile gene in Chinese cabbage (Brassica rapa L.) - Hui Feng; Peng Wei; Zhong-Yun Piao; Zhi-Yong Liu; Cheng-Yu Li; Yu-Gang Wang; Rui-Qin Ji; Shu-Juan Ji; Ting Zou; Su-Ryun Choi; Yong-Pyo Lim (Theoretical and Applied Genetics, 2009)

Genome-wide Comparisons of Gene Expression for Yield Heterosis in Maize - Bo Li; Deng-Feng Zhang; Guan-Qing Jia; Jing-Rui Dai; Shou-Cai Wang (Plant Molecular Biology Reporter, 2009)

Degraded vegetation and wind erosion influence soil carbon, nitrogen and phosphorus accumulation in sandy grasslands - Feng-Rui Li; Wen-Zhi Zhao; Ji-Liang Liu; Zhi-Gang Huang (Plant and Soil, 2009)

Quantification of Three Key Enzymes Involved in Artemisinin Biogenesis in Artemisia annua by Polyclonal Antisera-Based ELISA - Qing-Ping Zeng; Xiao-Mei Zeng; Lu-Lu Yin; Rui-Yi Yang; Li-Ling Feng; Xue-Qin Yang (Plant Molecular Biology Reporter, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

Cadmium Accumulation in the Edible Parts of Different Cultivars of Radish, Raphanus sativus L., and Carrot, Daucus carota var. sativa, Grown in a Cd-contaminated Soil - Rui-Lun Zheng; Hua-Fen Li; Rong-Feng Jiang; Fu-Suo Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

Characterization of donor genome contents of backcross progenies detected by SSR markers in rice - Zhang-Ying Xi; Feng-Hua He; Rui-Zhen Zeng; Ze-Min Zhang; Xiao-Hua Ding; Wen-Tao Li; Gui-Quan Zhang (Euphytica, 2008)

AtMTM1, a novel mitochondrial protein, may be involved in activation of the manganese-containing superoxide dismutase in Arabidopsis - Zhao Su; Mao-Feng Chai; Ping-Li Lu; Rui An; Jia Chen; Xue-Chen Wang (Planta, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

The impact of cropland conversion on environmental effect in the Loess Plateau: a pilot study based on the national experimental bases - Wang Fei; Li Rui; Jiao Feng; Yang Qingke; Tian Junliang (Journal of Geographical Sciences, 2005)

Activation of the gene promoter of barley β-1,3-glucanase isoenzyme GIII is salicylic acid (SA)-dependent in transgenic rice plants - Yun-Feng Li; Rui Zhu; Peilin Xu (Journal of Plant Research, 2005)

Pedoecological effects of a sand-fixing poplar (Populus simonii Carr.) forest in a desertified sandy land of Inner Mongolia, China - Feng-Rui Li; Hua Zhang; Li-Ya Zhao; Yasuhito Shirato; Xian-Zhi Wang (Plant and Soil, 2003)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)